Chlorine dioxide fumigation improves kiwifruit peel appearance by selectively depleting flavonoid pigments without compromising eating quality - Jiacheng Teng; Rui Chen; Xuening Wu; Yanfei Hu; Zhengchen Tian; Weisong Li; Wendong Zhang; Xiaomei Ji; Xiaoqin Yang; Xuping Gong; Tiantian Li; Xiaoyan Mao; et al. (Postharvest Biology and Technology, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Water quality assessment in multi-salinity groundwater of muddy coastal zones using a function-adaptive weight water quality index - Qiming Sun; Xinyue Chang; Rui Xu; Xin Ji; Jianhe Yang; Hongwei Liu; Maosheng Gao; Guohua Hou; Zhenlin Liu; Xianmin Ke; Jie Dong (Journal of Contaminant Hydrology, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Multiphase phosgene detection on machine learning-enhanced fluorescent sensor arrays - Rui Xiao; Kongqing Zhang; Dun Zhou; Jiaxuan Ma; Changchang Ji; Zhanhua Huang; Xiaobai Li; Yongpeng Liu; Hongwei Ma (Analytica Chimica Acta, 2026)

Biochar strengthens rainfall regime resistance of soil inorganic C by enhancing pH–bicarbonate and carbonic anhydrase regulation in dryland region - Yuhao Wang; Yanbo Ji; Shutong Guo; Lin Sun; Enke Liu; Zhikuan Jia; Kadambot H.M. Siddique; Rui Qian; Ting Wei; Peng Zhang (Agriculture, Ecosystems & Environment, 2026)

Enhancing resistance against white spot syndrome virus in Litopenaeus vannamei via recombinant Lactobacillus acidophilus through modulation of gut microbiota function - Hang Zhang; Wei Liu; Yi-Ning Cui; Pei-Min He; Ji-shun Yang; Rui Jia (Aquaculture, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Lithium recovery from weakly acidic high Na/Li ratio raffinate of spent battery recycling process by solvent extraction with P507 - Shuang Sun; Yuefeng Deng; Ji Chen; Yang Meng; Rui Qin; Zhongte Du (Hydrometallurgy, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

A depth-integrated OBS calibration method for high-concentration suspensions in estuaries - Jiawei Qu; Rui Huang; Wei Zhang; Chao Ji (Estuarine, Coastal and Shelf Science, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Intrusion dynamics of descending particle-laden plumes in stratified ambient: the roles of fluid buoyancy fraction and source momentum - Li Zhang; Yan Zhang; Xu-Hui Zhang; Ji-Yan Qiao; Yin-Rui Zhang; Xiao-Bing Lu (Environmental Fluid Mechanics, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Description of two novel Marinobacter species isolated from saline-alkali soil: Marinobacter alkalisoli sp. nov. and Marinobacter shunpengi sp. nov - Jing-Yan Zhao; Lian Xu; Rui-Qi Sun; Mei-Qian Song; Jia-Hui Zeng; Hua-Mei Wei; Ji-Quan Sun (Systematic and Applied Microbiology, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

A synthetic microbiome drives a multi-omics response to remediate 1,4-dithiane–contaminated soil and simultaneously suppresses antibiotic resistance genes - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Journal of Hazardous Materials, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Recent advances in electromechanical coupling functional metamaterials - Han Yan; Yi Zhang; Wei Zhong Jiang; Xiao Ji; Rui Zhu; Jing Bo Sun; Yi Min Xie; Ken E. Evans; Xin Ren (Engineering Structures, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Spatiotemporal dynamics of land degradation in the three gorges reservoir area and its coupling mechanisms with biodiversity and human activity intensity - Cuicui Ji; Hao Cui; Rui Ma; Dandan Ke; Xia Li; Fenglei Han; Xizeng Huang; Jie Liu; Gang Yang; Liejian Wang (CATENA, 2026)

Change of aerosol properties and transport mechanisms in Beijing during 2021-2024 - Rui Xu; Linlu Mei; Kai Ji; Gerrit de Leeuw; Zhibin Lai; Feiyang Wang; Yongliang Yang; Xinhong Zhang; Ruilai Nie (Atmospheric Pollution Research, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Remote sensing of rural clean heating impacts on air quality: An STL-Q3 framework in Henan Province, China - Yongliang Yang; Wenqiang Guo; Zhitao Zhou; Kai Ji; Zhibin Lai; Rui Xu; Feiyang Wang; Linlu Mei (Remote Sensing Applications: Society and Environment, 2026)

A Hausdorff-guided deep learning approach for tracking the motion of rotating Arctic ice floes - Adan Wu; Tao Che; Chengzhu Ji; Xiaowen Zhu; Rui Zhang; Jinlei Chen; Liuhao Wang; Qingchao Xu; Shengpeng Chen (Ocean Engineering, 2026)

Comprehensive time-frequency analysis of multistage and multiscale propeller cavitation-induced pressure impacts on the ship hull - Guoshou Zhao; Heng Liu; Rui Wu; Sheng Ji (Ocean Engineering, 2026)

Chronic exposure to Bisphenol AF from gestation through adulthood induces renal injury in 8-month-old mice via lipid metabolism dysregulation and ferroptosis - Rui Gao; Jiangsong Ma; Aonan Lu; Xiaoyun Wu; Chao Zhang; Keming Yun; Zhe Chen; Xiaotong Ji (Journal of Hazardous Materials, 2026)

Optimizing pe+pH via integrated water management and phosphorus fertilization enhances phytoextraction of Cd/As by rice plant in contaminated paddy soils - Rui Huang; Yunhe Xie; Xin Wang; Wei Wei; Bingyu Li; Jingmin Yang; Haoyu Chen; Saihua Liu; Xionghui Ji (Journal of Environmental Sciences, 2026)

Optimization of magnetic field-assisted freezing via response surface methodology and its impact on blueberry freeze-thaw quality - Bowen Chen; Xinqun Zhou; Jing Sun; Rui Wang; Min Zhang; Ning Ji; Tingchao Liu; Bangdi Liu; Lihua Jiang (International Journal of Refrigeration, 2026)

Multiphase flow dynamics and flow pattern analysis in production wellbore during subsurface carbon storage - Fengyuan Zhang; Zhenyang Ji; Ruihan Lu; Zhenhua Rui; Qiang Xia; Wenxing Cao (Fuel, 2026)

Corrigendum to “Effect of magnetic field-assisted curing on NaCl diffusion, protein structure, and quality attributes of beef” [Food Res. Int. 236 (2026) 119292] - Rui-Cheng Xu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Research International, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

In situ zwitterionic hydrogel coating of hollow fiber membranes for anti-fouling and efficient hemodialysis - Jinlong Xu; Boyang Xu; Rui Ji; Xian Xie; Zequn Gao; Xianglan Wu; Yongjian Li; Yuehong Li; Ho Cheung Shum; Haosheng Chen (Chemical Engineering Journal, 2026)

Enhancing treatment performance for agricultural runoff in ecological ditches through synergistic effects of denitrifying phosphate-accumulating bacteria and natural/synthetic media - Yonggui Zhao; Xiaoyun Sun; Bohua Ji; Ying Peng; Jingzhi Mao; Chenyu Zeng; Rui Yang; Junjun Chang (Journal of Cleaner Production, 2026)

Effect of magnetic field-assisted curing on NaCl diffusion, protein structure, and quality attributes of beef - Rui-Cheng Xu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Ran Feng; Bao Zhang (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Potential Zoning and Target Optimization of Geothermal Resources in the Eastern Margin of the Qinghai–Xizang Plateau: Multi-Source Data GIS Modeling Based on Fusion Machine Learning - Rui Cao; Renyu Gao; Qingwen Chen; Ji Dor; Qijun Liu; Yiming Yan; Huiren Meng (Natural Resources Research, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Microplastics enrich and disseminate antibiotic resistance genes in seawater: Enhanced effects of aging and biodegradability of microplastics - Jianhong Shi; Chengyuan Ji; Chaoli Sun; Changhai Jiang; Baoyi Lv; Rui Wang (Journal of Environmental Chemical Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Metabolic insights into the Fe/Mn-biochar assisted anammox-comammox process: Synergistic electron-transfer and structural resilience under nitrite starvation - Xurui Zhu; Xiaonong Zhang; Luomiao Ji; Rui Zhao; Bo Gao; Wen Sun; Peng Wu (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to “Climate risk exposure and green mergers and acquisitions: Evidence from China” [J. Environ. Manag. 396 (2025) 128068] - Huanyong Ji; Rui Zhang; Zhongzhen Miao (Journal of Environmental Management, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Influence of Pt-Cu synergistic action and TiO2 core–shell structure on NH3-SCO and anti-aging performance - Zhenhua Ji; Zhongqiang Bao; Zihao Wu; Peng Zhang; Rui Yang; Ding Luo; Hao Chen (Fuel, 2026)

Rfx5 acts as a master regulator of MHC class I and class II gene expression in zebrafish immunity - Rui Liu; Xiangmin Zhang; Xiu Yin; Ailong Zhang; Yunchao Wang; Lu Wang; Guangdong Ji; Hongyan Li (Fish & Shellfish Immunology, 2026)

Divergent mechanisms of zinc and manganese in controlling cadmium transfer to rice grain: from big data to field verification - Rui Liu; Shufang Pan; Xinliang Liu; Lei Luo; Ziqian Zhong; Qihong Zhu; Hanhua Zhu; Xionghui Ji; Daoyou Huang (Environmental Pollution, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

Ultra-low temperature adsorption of propane to achieve layered Ni3V2O8/NiO synergistic catalysed oxidative dehydrogenation of propane to propylene - Rui Liao; Yun Yang; Peiting Jiang; Fengyu Ji; Yuhang Qian; Lulu Li; Xuyu Wang; Xinwei Zhou; Hongbing Ji (Fuel, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Nitrogen and phosphorus limitation patterns of microbial nitrogen cycling traits in an arid soil - Hongfei Ji; Ying Wang; Rui Wang; Shengli Guo (Journal of Soils and Sediments, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

SB216763 enhances proliferation and sustains the undifferentiated state of porcine spermatogonial cells in prolonged In vitro culture - Benliang Zhou; Zhen Zhang; Anqin Duan; Jiaxiang Ji; Mengqi Li; Rui Chen; Xiangxing Zhu; Jianghua Shang; Xiaogan Yang; Xingwei Liang (Theriogenology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Life-cycle carbon footprints of rural toilet systems in China: Hotspot diagnosis and mitigation pathways - Rui Ma; Xiangwen Jia; Yilan Cheng; Sen Cen; Qian Wang; Zeye Zou; Fangying Ji; Xiaoming Wang (Journal of Cleaner Production, 2026)

Effective recovery of Dy from LiCl-KCl molten salt via controlled potential on Ga electrode: Mechanism, kinetics and thermodynamics of electrode reaction - Yuying Xiao; Wenlong Li; Rui Li; Ziqin Huang; Ming Gong; Jiandong Li; Ji Wang; Lifeng Chen; Shunyan Ning; Xiangbiao Yin; Wei Han; Yuezhou Wei (Journal of Environmental Chemical Engineering, 2026)

Multiphase flow model of CO2 and formation fluid for production wellbores in CO2 geological storage - Fengyuan Zhang; Wenxing Cao; Ruihan Lu; Zhenhua Rui; Tayfun Babadagli; Qiang Xia; Zhenyang Ji (Fuel, 2026)

Efficient regeneration of deactivated VPO catalysts: Reconstructing the catalyst active structure via a mild reduction-reoxidation-reaction stabilization process - Jiale Xu; Fei Wang; Renjie Ji; Xiaoyu Yan; Rui Huang; Chunyi Li (Chemical Engineering Journal, 2026)

Ferrate-assisted nonthermal plasma for efficient PFOA degradation in landfill leachate: Mitigating bulk organic interference and enhancing application potential - Changtao Chen; Zhuofan Yu; Rui Zhang; Xuetong Yang; Qintong Wang; Yuxian Ji; Xiaoyu Cheng; Jun Li; Anton Nikiforov; Stijn W.H. Van Hulle; Bo Lai (Water Research, 2026)

Broccoli plant elicitor peptide BoPep4 enhances plant salt tolerance by improving glucosinolate metabolism - Rui Li; Meihan Liu; Xiaoxue Hu; Jianing Li; Qiuying Pang; Xiufeng Yan; Jing Li; Wei Ji (Plant Science, 2026)

Oxidized- and hydroxylated-pennogenin saponins from the rhizomes of Paris fargesii and their hemostatic activity - Ling-Ling Yu; Lijin Jiao; Yan-Xi Li; Xu-Hong Li; Shan-Shan Ling; Long-Gao Xiao; Rui-Qi Liu; Wei Ni; Huan Yan; Yunheng Ji; Hai-Yang Liu (Phytochemistry, 2026)

Macro-micro scales insights into the effect of enrofloxacin on the Fe-C-Anammox system: Performance enhancement, metabolic optimization, and ARGs reduction - Rui Zhong; Jiaqi Lu; Liping Xie; Xiao-Ming Ji; Qi Zhang; Xiao Ma; Wenru Liu; Ying Wang (Journal of Water Process Engineering, 2026)

Alpaca nanobody-based sandwich ELISA for specific detection of Salmonella enteritidis in chicken - Liang Yuan; Shibo Wang; Yani Ren; Zhenghua Ji; Xinru Jiang; Beili Hao; Shuangshuang Hao; Xiaoxi Han; Changwen Li; Yicong Chang; Rui Li; Fangping Liu (Food Control, 2026)

Ecosystem-specific composition and drivers of plastisphere resistome in freshwater and marine environments - Jianhong Shi; Chaoli Sun; Yinglong Su; Yifan Wu; Min Zhan; Chengyuan Ji; Rui Wang; Baoyi Lv (Environmental Research, 2026)

Deriving predicted no-effect concentrations for PFASs to protect threatened and endangered fish: A comparison of water- andtissue-residue-based toxicity data - Jiayu Wang; Xiaolei Wang; Qingyuan Cao; Rui Wang; Yuanpu Ji; Jing Zhang; Fengchang Wu; Zugen Liu; Xiaoli Zhao (Environmental Research, 2026)

The couples' distinct effects of metals exposure on intermediate and pregnancy outcomes of in vitro fertilization treatment: A prospective cohort study - Qian Li; Xun Su; Zihan Xia; Duoxu Ji; Rui Dong; Tao Yin; Xinyu Yue; Dongyang Zhang; Yunxia Cao; Dongmei Ji; Chunmei Liang (Environmental Research, 2026)

A machine learning based predictive control framework for energy efficient fog prevention and humidity management in indoor ice rinks - Wenzhuang Liu; Jialing Song; Jiazhe Ji; Rui Yan; Zhiqiang Yin; Yaojun Li; Di Zhang (Energy and Buildings, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Correction to: Genetic Mapping of the Wheat Dimeric α-Amylase Inhibitor Multi-Gene Family Using Allele-Specific Primers Based on Intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Fungal diversity associated with Ulva pertusa and its response to cAMP and light - Rui Guo; Yinping Song; Weicheng Xu; Naiyun Ji (Journal of Oceanology and Limnology, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Chronic co-exposure to BPA and alcohol synergizes hepatotoxicity via dysregulation of glycerolipid metabolism and ceramide/HtrA2-driven apoptosis in HepG2 cells - Yan Qin Tan; Chia-Lung Shih; Yi-Chia Chen; Sheng-Han Lee; Ji-Rui Yang; Chan-Yen Kuo; Yi-Shiou Chiou (Journal of Hazardous Materials, 2026)

New insights into the interaction between bacterioplankton community and dissolved organic matter driven by river connectivity - Jianghao Ji; Xiong Cao; Rui Wang; Jianguo Tao; Mochen Wu; Yuanze Sun; Jiangyong Chu; Xin Kou; Xiaofeng Cao; Jie Wang; Jianfeng Peng (Journal of Environmental Management, 2026)

Cadmium adsorption-desorption synergy drives spatial heterogeneity of grain cadmium enrichment in a subtropical limestone paddy region - Xinliang Liu; Shufang Pan; Rui Liu; Lei Luo; Ziqian Zhong; Qihong Zhu; Xionghui Ji; Daoyou Huang (Environmental Pollution, 2026)

Alkali-induced molecular aggregation enabled rapid-forming PVA hydrogel electronic skin with multifunctional integration of protection, EMI shielding, and sensing - Di Liu; Yang Lyu; Zhongying Ji; Rui Guo; Zhihan Hong; Xiaolong Wang; Xinyan Shi (Chemical Engineering Journal, 2026)

Patterns of phoD- and pqqC-containing bacterial communities and their potential linkages with soil P cycle multifunctionality under long-term crop rotations - Hongfei Ji; Yan Chen; Ying Wang; Rui Wang; Shengli Guo (Plant and Soil, 2026)

A critical review of inhibitory effects of substrates and organic matter on anammox: mechanisms and mitigation strategies - Rui Zhao; Da Jin; Xiaonong Zhang; Luomiao Ji; Xurui Zhu; Bo Gao; Peng Wu (ENGINEERING Environment, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Spatiotemporal modeling of oxygen transport and layered regulation in tidal flow constructed wetlands - Rui Ma; Lanlan Fu; Jiangsen Ma; Lei Jiang; Yiyuan Zhuo; Linsong Cheng; Fangying Ji; Xiaoming Wang (Water Research, 2026)

Brominated organic compounds in leachate across China: Occurrence and molecular variations - Jing Zheng; Ji-Tao Lv; Yue Sun; Qing-Yu Liu; Qiu-Rui Zhang; Zi-Meng Wang; Xiao-Song He (Water Research, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Straw incorporation mitigates polyethylene residual film-induced suppression of fungal necromass - Conghui Liu; Yapeng Jiao; Hanyu Guo; Yunli Ji; Rui Yin; Yongxiang Yu; Jianglan Shi; Xiangtian Meng; Xiaohong Tian (Journal of Hazardous Materials, 2026)

A Janus-interface origami fog collector with spike arrays for efficient droplet transport - Ji QI; Congji ZHANG; Rui SONG; Muneerah Alomar; Tianze ZHANG; Yuxiang CHEN; Jiachang CUI; Shangzhen XIE; Zhiguang GUO (Chemical Engineering Journal, 2026)

Machine learning-assisted the directed evolution of descriptor for Mg-CO2 batteries - Zhe Xue; Rui Tan; Ming Ji; Jinzhong Tian; Hua Hou; Xinyu Zhang; Lianfeng Zou; Yuhong Zhao (Chemical Engineering Journal, 2026)

Hofmeister effect-regulated poly(vinyl alcohol) @ cellulose nanofiber hydrogel-based SERS enhancement and sensing application - Changyan Tan; Rui Li; Qin Yang; Lu Xue; Yong Ye; Ji Zhou; Ning Lin (Carbohydrate Polymers, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

Study of Ice Load on Hull Structure Based on Full-Scale Measurements in Bohai Sea - Guanhui Zhao; Cuina Zhao; Xiang Xia; Rui Lin; Shuaikang He; Xiaodong Chen; Shunying Ji (Journal of Marine Science and Engineering, 2025)
Ice load is a crucial factor when designing structures for polar vessels. Due to the unpredictable nature of sea ice mechanics and the complexity of ship structures, obtaining ice load characteristics through full-scale measurements is considered more effective and reliable. However, conducting full-scale tests in the Arctic for China can be time-consuming and expensive. Using the natural ice fields in the Bohai Sea for full-scale tests can provide valuable insights into the study of ice load. To study ice load characteristics, full-scale measurements were carried out during icebreaker navigation trials in the ice zone of Bohai Sea. Distributed shear strain sensors were installed to measure the ice-induced structural strain on the starboard of the bow, and the local ice loads were determined based on the influence coefficient matrix method. Additionally, video cameras were utilized to record ice conditions, including ice type and thickness. By analyzing the data, the Rayleigh separation method was used to extract the process of ice load action. Statistical analysis was performed on the peak ice load values, with a particular emphasis on the various types of sea ice, ice thickness, and ship speed. The results show that the action period, peak value, mean value, and waveform of ice loads obtained in the full-scale measurement are consistent with the full-scale data of other icebreakers. The conclusion supports the effectiveness and feasibility of conducting ship ice load characteristic testing in the Bohai Sea.

A registration and construction quality analysis framework for low quality hull block point cloud with extensive redundant structures - Shilin Huo; Ji Wang; Rui Li; Yujun Liu; Lin Pang; Jian Zhang (Ocean Engineering, 2025)

Numerical calculation of line heating for hull curved plate based on strain direct boundary - Shun Wang; Haohao Jia; Yuxuan Fu; Ji Wang; Rui Li (Ocean Engineering, 2025)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

RETRACTED: Climate risk exposure and green mergers and acquisitions: Evidence from China - Huanyong Ji; Rui Zhang; Zhongzhen Miao (Journal of Environmental Management, 2025)

Synergistic solvent–salt strategy enables high-efficiency dehydration and recovery of 2,3-butanediol from aqueous media - Yuxia Ji; Rongze Lin; Yanyuan Yin; Xuejiao Yang; Rui Lang; Shaoqu Xie; Yanxiong Fang (Journal of Environmental Chemical Engineering, 2025)

A critical review of biochar-enhanced Feammox: Multilevel mechanisms and sustainable applications for nitrogen removal - Luomiao Ji; Xiaonong Zhang; Rui Zhao; Xurui Zhu; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Detection and degradation of bisphenols in honey using matrix-induced dispersive liquid-liquid microextraction: Insights into the release of bisphenol A from polycarbonate microplastics - Ji Yang; Yuchang He; Chunping Du; Yuqing Zuo; Lingfei Xie; Ping Yan; Rui Dong; Xijuan Tu; Wenbin Chen (Environmental Pollution, 2025)

Synergistic confinement and heavy atom effects in carbon dots for enhanced phosphorescence: Matrix-free and matrix conditions - Rui Li; Linping Zhang; Ji Fan; Bijia Wang; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

3D printed hydrogel with fingerprint-inspired features for enhanced sensing performance in electronic skin - Jianshe Hao; Yanbin Xu; Chaofan Yang; Rui Guo; Yang Lyu; Zhongying Ji; Xiaolong Wang (Chemical Engineering Journal, 2025)

A new isopropanol-intermediate mechanism for CO2-assisted propane dehydrogenation over ZIF-derived (GaCe)Ox: Toward propylene synthesis - Yun Yang; Rui Liao; Rulan Pu; Peiting Jiang; Lulu Li; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Protection against intestinal damage in female Drosophila melanogaster: Comparative contribution of arabinoxylan and its non-covalent/covalent complexes with catechin - Dima Atehli; Tianyu Qi; Rui Liu; Wan Wang; Qiaomei Zhu; Yuanlin Sun; Qingbin Guo; Ji Kang (Bioactive Carbohydrates and Dietary Fibre, 2025)

Interplay between Nrf2 and ROS in regulating epithelial-mesenchymal transition: implications for cancer metastasis and therapy - Yi Xu; Shuning Hu; Rui Chen; Sheng Xu; Guangyang Yu; Lili Ji (Molecular Biology Reports, 2025)
Epithelial-mesenchymal transition (EMT), including developmental (Type I), wound healing (Type II), and pathological (Type III) subtypes, constitutes a critical driver of cancer metastasis. This review analyzes the redox interplay between nuclear factor erythroid 2-related factor 2 (Nrf2) and reactive oxygen species (ROS) in EMT regulation and cancer progression. Nrf2 maintains redox homeostasis through antioxidant gene activation while paradoxically promoting tumor survival and drug resistance via Keap1-dependent degradation and phosphorylation-mediated stabilization. ROS generated through mitochondrial and NADPH oxidase pathways exhibit dual functionality: moderate levels activate EMT transcription factors to drive metastasis and cancer stem cells (CSCs) plasticity, whereas excessive ROS induce apoptosis and ferroptosis. While Nrf2 typically suppresses EMT through ROS neutralization and epithelial integrity preservation, chronic Nrf2 activation in CSCs paradoxically sustains metastatic potential through redox buffering. This synthesis delineates the spatiotemporal regulation of Nrf2-ROS-EMT networks across tumor microenvironments, emphasizing therapeutic opportunities through redox balance modulation and pathway-specific Nrf2 inhibition in advanced malignancies.

CLDN4 promotes ferroptosis and inflammation involving JAK2/STAT3 pathway in acute pancreatitis - Chuanming Zheng; Rui Tao; Zhenjie Wang; Xi Zhang; Hai Jiang; Zhong Ji; Hehe Dou; Zhaohui Du (Functional & Integrative Genomics, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Regional economic globalization patterns and evolution of the Pearl River Delta: A perspective of strategic coupling - Yi Liu; Yingtiao Liu; Jiehan Ji; Shengjun Zhu; Rui Chen (Journal of Geographical Sciences, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Injectable Hyaluronic Acid Hydrogels Crosslinked by Structure-engineered Aldehyde-functionalized β-Cyclodextrin Derivatives for Long-term Controlled Voriconazole Delivery - Chao Yang; Meng Xin; Yufu Jiang; Wenqian Wang; Wenhui Li; Junlin Quan; Wancong Zhou; Rui Yuan; Zhe Chen; Depeng Shi; Zhijian Ji; Xingxing Yue; et al. (AAPS PharmSciTech, 2025)

Understanding orbital pacing, uplift dynamics, and oceanic influences in aeolian red clay sediments over the Chinese Loess Plateau through cyclostratigraphy insights - Xiaohao Wei; Rui Zhang; Vadim A. Kravchinsky; Joseph V. Ferraro; Jie Qin; Minghao Ma; Dongyue Zhang; Xiaojuan Li; Leping Yue; Jianxing Li; Yong Xu; Ji Ma; et al. (International Geology Review, 2025)

Dynamics of multiple rogue waves for (3+1)-dimensional variable-coefficient potential Yu-Toda-Sasa-Fukuyama equation - Yi-Lin Tian; Wen-Yuan Li; Nong-Sen Li; Rui-Gang Zhang; Ji-Feng Cui (Wave Motion, 2025)

Prediction method of propeller tip vortex cavitation inception based on bubble dynamics models and change-point detection - Jia Duan; Rongwu Xu; Lilin Cui; Bin Ji; Rui Wu; Heng Liu; Chang Chen (Ocean Engineering, 2025)

Hydrodynamic force analysis of semi-submerged propeller and influence on shaft whirling vibrations - Fangshuai Wei; YuJun Liu; Ji Wang; Rui Li; Lin Pang (Ocean Engineering, 2025)

PFAS in bottled water from China: High prevalence of ultrashort-chain compounds, health risks, and global insights - Haoting Quan; Fahui Ji; Zhen Zhong; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Elucidation of the molecular mechanism for the phenolic acid removing the fishy odor bound to proteins in sea bass - Huanqing Lei; Yaoxing Chen; Rui Wang; Qiaohui Zeng; Langhong Wang; Jian Li; Wenhao Lin; Xinan Zeng; Zhong Han; Ji Ma; Ruoyong Wang (Food Chemistry, 2025)

Sealing performance of air plugs in abandoned coal mine tunnels for compressed air energy storage - Xiaohu Chen; Wei Liang; Rui Sun; Bowen Hu; Yukun Ji (Engineering Geology, 2025)

Revealing the differences and similarities in the in-situ and ex-situ activation of VPO catalysts to further optimize the activation process - Jiale Xu; Renjie Ji; Xiaoyu Yan; Rui Huang; Fei Wang; Jianxiang Li; Chunyi Li (Chemical Engineering Journal, 2025)

Field analysis of PM2.5 infiltration factor and determinants of indoor concentrations in residential buildings within a mega-city in southern China - Jingjin Shi; Yanling Shen; Rui Yuan; Jing Cai; Jianbang Xiang; Xinhua Ji; Zhuohui Zhao (Atmospheric Environment, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Enhanced performance of algal-bacterial granular sludge in treating wastewater under PFOA stress: Synergistic effects and mechanisms - Fahui Ji; Xiaojing Yang; Haoting Quan; Jinxia Liu; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Advances in the application of carbon materials for anammox enhancement: A comprehensive review - Bo Gao; Xiaonong Zhang; Rui Zhao; Xurui Zhu; Luomiao Ji; Peng Wu (Journal of Environmental Management, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

“Phenology description is all you need!” mapping unknown crop types with remote sensing time-series and LLM generated text alignment - Siyuan Wen; Wenzhi Zhao; Fengcheng Ji; Rui Peng; Liqiang Zhang; Qiao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Bioactivity of essential oils extracted from four varieties of Zanthoxylum bungeanum against insects and dominant spoilage fungi in Codonopsis pilosulae - Rui Feng; Zhenjia Ma; Jiali Bai; Jie Fan; Chunyu HE; Junlong Wang; Ji Zhang; Junyu Liang; Feng Zhou (South African Journal of Botany, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Mechanistic insights into the impact of Lincomycin on microalgal-bacterial granular sludge in domestic wastewater treatment - Guihua Wang; Shujuan Meng; Bin Ji; Rui Wang; Min Liao; Xinyu Chang; Yu Liu; Meng Zhang (Journal of Water Process Engineering, 2025)

Moderate ozone application preserves postharvest quality of ‘manaohong’ cherries by enhancing antioxidant defense and membrane stability - Wei Zou; Ning Ji; Yuxin Li; Huali Nie; Qi Gao; Rui Wang; Cunkun Chen; Bangdi Liu (Journal of Stored Products Research, 2025)

Sub-soil biodegradable film mulching: A sustainable solution for enhancing winter wheat yield and shaping soil microbial communities in saline-alkali soils - Changyuan Wang; Junwei Dong; Boxiang Ji; Yahui Lv; Yixuan Song; Quanqi Li; Chitao Sun; Rui Zong; Mingming Zhang (Journal of Hazardous Materials, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Catalytic dehydrogenation of propane by electrospinning one-dimensional Zn-Ga2O3-Al2O3 nanofibres under CO2 atmosphere - Rui Chen; Xue Han; Yixuan Yang; Xupeng Yang; Yuqi Wang; Yupeng Zhang; Tiange Huang; Jie Wei; Junjie Ding; Xuyu Wang; Hongbing Ji (Fuel, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Electrochemical CO2 reduction via strain-engineered AuPd alloy catalysts - Shangdong Ji; Qian Wang; Jiapeng Huang; Ruiyun Guo; Yanan Li; Yangzi Zheng; Rui Li; Yaohui Zhao; Chao Wu; Mingshang Jin (Chemical Engineering Journal, 2025)

Doping potassium to modulate the surface properties of CuO/SiO2 for selective oxidation of isobutane to tert-butanol - Renjie Ji; Jiale Xu; Rui Huang; Xiaoyu Yan; Fei Wang; Chunyi Li (Chemical Engineering Journal, 2025)

Enhancing Mnammox-driven nutrient removal in manganese ore-based constructed wetlands: The electron-shuttling role of straw-released humus - Rui Ma; Yiyuan Zhuo; Jintao Lei; Lanlan Fu; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2025)

Effects of geographical and soil factors on soilś arsenic levels: a case study in typical arsenic-contaminated paddy fields based on machine learning - Renjie Zhang; Liheng Jiang; Tianhao Dong; Yunhe Xie; Shufang Pan; Saihua Liu; Rui Huang; Xionghui Ji; Tao Xue (Environmental Management, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

Effects of Penthorum chinense pursh and gallic acid on embryonic and cardiac development in zebrafish (Danio rerio) - Kehui Liu; Hui Jiang; Rong Ji; Yuanyuan Ma; Rui Zhang; Binbin Song; Ying Han (Toxicology in Vitro, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Insights into ROL-driven and ROS-mediated metalloid oxidation and sequestration in the soil-rice iron barrier system - Jing-Min Yang; Xin Wang; Dong-Xing Guan; Rui Huang; Xiong-Hui Ji; Yun-He Xie; Bo Peng; Qin-Bo Qin (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Laodelphax striatellus salivary sheath protein Lsactin triggers defense response in plants - Liangxuan Qi; Jing Li; Han Wang; Jing Li; Xinyang Tan; Zhichang Zhao; Sicong Zhou; Jichao Fang; Rui Ji (Insect Biochemistry and Molecular Biology, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

The combined application of cis-cyclo(L-Phe-L-Pro) with antimicrobial proline-based 2,5-diketopiperazines significantly enhances anti-breast cancer activity by selectively targeting cancer stem cells - Rui Liu; Bo Sun; Sa-Ouk Kang; Yeonju Hong; Ji-Yoon Yeo; Jun-Hua Wang; Min-Kyu Kwak (Chemico-Biological Interactions, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

Critical roles of rare species in the anaerobic ammonium oxidizing bacterial community in coastal sediments - Yu Zhang; Mingming Chen; Rui Du; Ehui Tan; Shuh-Ji Kao; Yao Zhang (Marine Life Science & Technology, 2025)
Anaerobic ammonium oxidation (anammox) plays a critical role in nitrogen loss in estuarine and marine environments. However, the mechanisms underlying the formation and maintenance of the anammox bacterial community remain unclear. This study analyzed the anammox bacterial diversity, community structure, and interspecific relationships in three estuaries along the Chinese coastline —the Changjiang Estuary (CJE), the Oujiang Estuary (OJE), and the Jiulong River Estuary (JLE) — as well as the South China Sea (SCS) to elucidate their community assembly mechanisms. The results indicated that the anammox bacterial community exhibited the highest ammonium concentration as well as the Shannon’s diversity index reflecting both species richness and evenness in the JLE. The lowest Shannon index was observed in the SCS. However, the anammox bacterial species richness was greatest in the CJE. Candidatus Scalindua was the predominant anammox bacteria identified in the coastal sediments, especially in the SCS sediments. Candidatus Brocadia and Candidatus Kuenenia were more abundant in the estuarine sediments, particularly in JLE, than in the SCS. Phylogenetic analysis revealed distinct differentiation among Candidatus Scalindua, Candidatus Brocadia, and Candidatus Kuenenia, with the former exhibiting a greater level of diversity. There was significant spatial heterogeneity in the anammox bacteria across the four regions, characterized by distinct distribution patterns for rare species. Low-abundance (rare) bacteria thrived in their native habitats, whereas abundant taxa displayed greater dispersal capabilities. An analysis of the community assembly mechanism suggested that ecological drift predominantly shaped the overall anammox bacterial community in the coastal sediments. Rare species were more susceptible to dispersal limitations and environmental selection. Co-occurrence network analysis identified Candidatus Scalindua as a keystone genus and highlighted that rare species may play a crucial role in maintaining the ecological stability of the anammox bacterial community in coastal sediments.

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

Reduced serum levels of mitochondria-derived peptide MOTS-c in patients with obstructive sleep apnea - Zhuoding Luo; Rui Ji; Renjing Ye; Yawen Shi; Qingfeng Pang; Min Yin (Sleep and Biological Rhythms, 2025)

A Computational Study on the Excitation Forces of Partially Submerged Propellers for High-Speed Boats - Fangshuai Wei; Yujun Liu; Ji Wang; Rui Li; Lin Pang (Journal of Marine Science and Engineering, 2025)
During high-speed navigation, boat propellers often become partially exposed due to elevated sailing speeds. This condition results in a unique operational scenario where propellers are only partially submerged. Conducting computational studies on the excitation of propellers under such circumstances is essential for optimizing the dynamic performance of the shafting system. A theoretical calculation method for propeller performance was developed based on the principles of fluid dynamics relevant to water entry, leading to a computational method for determining excitation forces in this specific operational condition. This method was subsequently refined through appropriate adjustments using ANSYS Fluent software to simulate the behavior of partially submerged propellers. The findings highlighted the accuracy of the proposed model in predicting the pulsation of six force components across three distinct directions: along the propeller shaft, vertical, and lateral. Specifically, for a single blade (Blade 1), the pulsation amplitude of the vertical force (Fx) constituted 82.1% of its maximum peak magnitude and equated to 57.5% of the blade’s mean thrust. Analogously, the lateral force (Fz) pulsation amplitude represented 53.3% of its maximum peak magnitude and 40.0% of the mean thrust. These findings indicate the presence of significant unsteady hydrodynamic loads. Furthermore, a visualization approach was presented to analyze blade load phasing, offering insights relevant to the arrangement of blades on partially submerged propellers.

Corrigendum to “Evaluation of the main economic characteristics of a narrow-thallus strain of Neoporphyra haitanensis” [Aquaculture Volume 558: 738395, 15 September 2022] - Rui Zhao; Yan Xu; Kai Xu; Dehua Ji; Changsheng Chen; Wenlei Wang; Chaotian Xie (Aquaculture, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

Assessing the contribution of VOCs to SOA formation and identifying their key species during ozone pollution episodes in a typical petrochemical city - Xiaoyu Yan; Fuhong Gao; Yuanyuan Ji; Cong An; Rui Gao; Yanqin Ren; Junling Li; Xiaoshuai Gao; Likun Xue; Fanyi Shang; Jidong Li; Hong Li (Environmental Pollution, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Artificial intelligence method for automatic classification of vibration signals in the mining process - Rui Dai; Jie Shao; Da Zhang; Hu Ji; Yi Zeng (Applied Geophysics, 2025)

Research on the Forming Detection Technology of Shell Plates Based on Laser Scanning - Ji Wang; Baichen Wang; Yujun Liu; Rui Li; Shilin Huo; Jiawei Shi; Lin Pang (Journal of Marine Science and Engineering, 2025)
In order to solve the problems of low efficiency and insufficient accuracy of the traditional manual template method in the forming detection of shell plates, a digital solution based on laser scanning detection system was proposed. By introducing a six-degree-of-freedom robotic arm and a high-precision line laser sensor to build a three-dimensional detection platform, a digital template method framework including data acquisition, point cloud registration, surface reconstruction, and deviation analysis was innovatively constructed. A point cloud non-penetration registration algorithm fused with boundary geometric information was proposed. Based on the improved Delaunay triangulation algorithm, the surface is reconstructed and the digital template is extracted. Experimental verification shows that the method achieves an accuracy of less than 1 mm of error in the detection of outer plates, shortens the single detection time to less than 10 min, and improves the detection efficiency by more than 75% compared with the traditional method.

Three-Dimensional Spatio-Temporal Slim Weighted Generative Adversarial Imputation Network: Spatio-Temporal Silm Weighted Generative Adversarial Imputation Net to Repair Missing Ocean Current Data - Yiwan Yue; Juan Li; Yu Zhang; Meiqi Ji; Jingyao Zhang; Rui Ma (Journal of Marine Science and Engineering, 2025)
Three-dimensional ocean observation is the foundation for accurately predicting ocean information. Although ocean observation sensor arrays can obtain internal data, their deployment is difficult, costly, and prone to component failures and environmental noise, resulting in discontinuous data. To address the severe missing data problem in three-dimensional ocean flow fields, this paper proposes an unsupervised model: Three-dimensional Spatio-Temporal Slim Weighted Generative Adversarial Imputation Network (3D-STA-SWGAIN). This method integrates spatio-temporal attention mechanisms and Wasserstein constraints. The generator captures the three-dimensional spatial distribution and vertical profile dynamic patterns through the spatio-temporal attention module, while the discriminator introduces gradient penalty constraints to prevent gradient vanishing. The generator strives to generate data that conforms to the real ocean flow field, and the discriminator attempts to identify pseudo-ocean current data samples. Through the adversarial training of the generator and the discriminator, high-quality completed data are generated. Additionally, a spatio-temporal continuity loss function is designed to ensure the physical rationality of the data. Experiments show that on the three-dimensional flow field dataset of the South China Sea, compared with methods such as GAIN, under a 50% random missing rate, this method reduces the error by 37.2%. It effectively solves the problem that traditional interpolation methods have difficulty handling non-uniform missing and spatio-temporal correlations and maintains the spatio-temporal continuity of the current field’s three-dimensional structure.

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

Study on freeze-thaw resistance and Na+ leaching characteristics of red mud-fly ash-phosphogypsum multiple solid waste road base material - Shengjie Liu; Dahu Rui; Mintae Kim; MingChang Ji; Jun Zhang; Pengfei Zhang (Cold Regions Science and Technology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Simulating oasis-desert interactions in artificial and natural oasis-desert areas: Integration of remote sensing data and CFD methodology - Zhixing Peng; Shaomin Liu; Rui Liu; Xinlei He; Jin Ma; Ziwei Xu; Ji Zhou; Dongxing Wu (Agricultural and Forest Meteorology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Integrating an innovative geothermal-driven multigeneration approach and LNG cold energy utilization process for sustainable energy supply, producing hydrogen, power, heating, and cooling - Jing You; Rui Xiao; Majed A. Alotaibi; Sohaib Tahir Chauhdary; Tiancheng Ji (Process Safety and Environmental Protection, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Corrigendum to ‘Transcriptomic and metabolomic analyses insight into the synergistic effects of nitric oxide and hydrogen sulfide fumigation on enhancing postharvest antioxidant defense and phenylpropane metabolism in ‘crystal’ grape’ [Food Bioscience, Volume 66, April 2025, 106110] - Renchan Liu; Ning Ji; Rui Wang; Yuxin Li; Huali Nie; Cunkun Chen; Bangdi Liu (Food Bioscience, 2025)

Transcriptomic and metabolomic analyses insight into the synergistic effects of nitric oxide and hydrogen sulfide fumigation on enhancing postharvest antioxidant defense and phenylpropane metabolism in ‘crystal’ grape - Renchan Liu; Ning Ji; Rui Wang; Yuxin Li; Huali Nie; Cunkun Chen; Bangdi Liu (Food Bioscience, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Pharmacological Inhibition of TXNRD1 by a Small Molecule Flavonoid Butein Overcomes Cisplatin Resistance in Lung Cancer Cells - Rui Yang; Shibo Sun; Qiuyu Zhang; Haowen Liu; Ling Wang; Yao Meng; Na Chen; Zihan Wang; Haiyan Liu; Fengyun Ji; Yan Dai; Gaohong He; et al. (Biological Trace Element Research, 2025)

Bacillus safensis M01 reversed the inflammatory injury of mice jejunum caused by enterotoxigenic Escherichia coli K88 - Xin-Wen Hou; Jinxin Meng; Xiao-Tong Chen; Ji-Xin Zhao; Kai-Meng Shang; Yong-Jie Wei; Rui Liu (Archives of Microbiology, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Developing a quantitative adulteration discrimination model for forest-grown Panax notoginseng using near-infrared spectroscopy with a dual-branch network - Chao Ji; Haoran Ba; Jinran Dai; Yuxin Xie; Tongyu Zang; Yi Sun; Rui Shi; Liangjuan Zhao; Min Yang; Xiahong He; Xiangyun Ma; Wenjie Zheng (Food Research International, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Highly stretchable, conductive, and self-adhesive starch-based hydrogel for high-performance flexible electronic devices - Rui Chen; Lei Wang; Dan Ji; Mengqing Luo; Zihao Zhang; Guiyan Zhao; Xiaohua Chang; Yutian Zhu (Carbohydrate Polymers, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Relative contributions of climate and grazing to forage supply in the Yellow River source area - Suizi Wang; Jiangwen Fan; Miaomiao Wang; Rui Tang; Nan-Ji Jiang (Journal of Environmental Management, 2025)

Anammox sludge granulation and synergy with comammox: A critical review - Rui Zhao; Xiaonong Zhang; Da Jin; Xurui Zhu; Luomiao Ji; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Piezoelectric polarization-induced photogenerated carriers transfer coupled with active electron transport Z-scheme heterojunction synergistic optimization of BiFeO3/CdS composite photocatalysts for hydrogen production - Xinyu Ma; Rui Li; Zhao Li; Long Zhang; Yongjie Cao; Kui Nie; Die Zhou; Qing Ji; Cheng Wang; Zehua Zhang; Yutian Li; Meidan Que; et al. (Journal of Environmental Chemical Engineering, 2025)

High slab thermal gradient facilitates dehydration and megathrust ruptures in the Solomon Sea plate - Weiling Zhu; Yingfeng Ji; Lijun Liu; Rui Qu; Ye Zhu (Journal of Asian Earth Sciences, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

RNA-Seq-based WGCNA reveals the physiological and molecular responses of poplar leaves to NaHCO3 stress - Song Jiaqi; Wang Jiechen; Qin Rui; Ji Guangxin; Cui Congcong; Sun Nan; Qi Siyue; Ding Changjun; Zhang Huihui (Trees, 2025)

Thirty-year dryland crop rotation improves soil multifunctionality and shifts soil fungal community - Ying Wang; Hongfei Ji; Yan Chen; Rui Wang; Shengli Guo (Plant and Soil, 2025)

Factors governing bark tufa deposition in fluvial systems: the case study of Nuorilang in Jiuzhaigou, Sichuan China - JunHao Li; FuDong Wang; WuYang He; QinYingZi Cai; Shi Chen; GuoQing Huang; Dawood Muhammad; Carlos Pérez-Mejías; Rui Zhang; ZiTong Peng; SiRui Chen; ChenWei Ji; et al. (Carbonates and Evaporites, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Spatiotemporal estimates and health risks of atmospheric trace metals across Hong Kong during 2016–2020 - Wenwen Sun; Shenghua Zhang; Dongmei Cai; Liqiang Wang; Ji Jin; Rui Li; Zhenghu Chen (Air Quality, Atmosphere & Health, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Dynamic Characteristics of Bidirectional Misaligned Marine Water-Lubricated Bearings Considering Turbulence, Surface Roughness and Bush Deformation - Ziqi Chen; Ji Wang; Rui Li; Yujun Liu (Journal of Marine Science and Engineering, 2025)
The marine water-lubricated bearing’s (WLBs) dynamic properties are essential for ensuring the shaft system’s operational dependability. The coupled model of mixed lubrication and turbulence under the impact of bidirectional misalignment is proposed in this research, and the perturbation equations of marine WLBs with 32 coefficients are derived. The finite difference method (FDM) is used to solve the steady-state and perturbation equations, and the impacts of turbulence, bearing bush deformation, surface roughness, and bidirectional shaft misalignment on the dynamic characteristics of the WLBs are systematically investigated. The results reveal that under mixed lubrication, surface roughness and the turbulence effect can both greatly improve the stiffness and damping of the bearings, but that there is a threshold phenomenon for the turbulence effect’s influence on these properties. Neglecting the elastic deformation of the bush may lead to an overestimation of the bearings’ stiffness and damping, causing substantial inaccuracies in conditions of heavy load or declined Young’s modulus. The 32 coefficients of the WLB exhibit considerable variation with the misalignment angle; hence, a more comprehensive dynamic model should be developed for misaligned marine WLBs. The study’s findings provide valuable insights for rotor dynamics research and optimal design of lubrication performance in marine WLBs.

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

Utilizing large language models for identifying future research opportunities in environmental science - Xiaoliang Ji; Xinyue Wu; Rui Deng; Yue Yang; Anxu Wang; Ya Zhu (Journal of Environmental Management, 2025)

The source and differential enrichment mechanisms of lithium in Gudui geothermal field: Constraints from enrichment and dilution processes of geothermal-type lithium - Rui Cao; Yiming Yan; Ji Dor; Qijun Liu; Yongqiang Cai; Shuangshuang Wan; Defan Chen (Geothermics, 2025)

Distribution and genesis of geothermal waters in the Xianshuihe fault zone, Western Sichuan plateau, China: Constraints on fracture system and regional seismic activities - Rui Cao; Yongqiang Cai; Ji Dor; Qijun Liu; Mariia Poliakova; Defan Chen; Shuangshuang Wan; Yiming Yan (Geothermics, 2025)

Role of a noval amadori rearrangement product: N- (1-deoxy-D-fructos-1-yl) -γ-aminobutyric acid in changing the taste of Huangjiu - Gang Han; Zhilei Zhou; Rui Chang; Qingxi Ren; Zhongwei Ji; Xibiao Xu; Yuezheng Xu; Jian Mao (Food Bioscience, 2025)

Peptidomics and computational peptidology insights into the taste peptide profile of different extraction methods: A case study of fermented rice wine (Huangjiu) - Rui Chang; Zhilei Zhou; Yuezheng Xu; Xibiao Xu; Zhongwei Ji; Shuangping Liu; Jian Mao (Food Bioscience, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

Spatiotemporal deformation analysis of glaciers and surrounding landscapes in the Shishapangma region using InSAR techniques - Wenli Liang; Rui Liu; Qin Ji; Pinglang Kou (Journal of Mountain Science, 2025)

Are air travelers willing to pay for mandatory carbon emission policies? Evidence from China - Bao-Jun Tang; Rui Yan; Jun-Yu Chen; Chang-Jing Ji (Sustainable Production and Consumption, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Enhanced detection of 4-nitrophenol in drinking water: ECL sensor utilizing velvet-like graphitic carbon nitride and molecular imprinting - Rui Xu; Yu Su; Hongfei Ji; Man Jiang; Ruizhong Zhang; Lan Ding; Yanhua Chen; Daqian Song (Food Chemistry, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Iron-doped diesel exhaust early-in-life inhalation-induced cardiopulmonary toxicity in chicken embryo: Roles of ferroptosis and acyl hydrocarbon signaling - Siyi Wang; Xinxian Gong; Junhua Yuan; Jing Huang; Rui Zhao; Jing Ji; Meinan Wang; Xiaoyu Shi; Wenya Xin; Yuxu Zhong; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2024)

Frictional contact-vibration coupling model for tbm rock cutting with multi-cutter - Meng-qi Zhang; Rui-xue Sun; Ji-liang Mo; Zhong-rong Zhou (Computers and Geotechnics, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Clinical significance and potential mechanism of hsa_circ_0006892 in acute respiratory distress syndrome complicated with pulmonary fibrosis - Shuping Zhang; Lingbo Rong; Guangwen Long; Feihong Huang; Qian Zhang; Xiulin Yang; Hongpeng Sun; Chunling Ji; Rui-hai Ye (Molecular Biology Reports, 2024)

Analysis of deliquescent chloride salt by laser-induced breakdown spectroscopy with controlled uniform precipitation - Lizhu Kang; Ji Chen; Zhijie Huang; Zhanjian Lin; Rui Zhang; Bing Lu; Xiangyou Li (Analytica Chimica Acta, 2024)

Novel insights into Feammox coupled with the NDFO: A critical review - Luomiao Ji; Xiaonong Zhang; Xurui Zhu; Bo Gao; Rui Zhao; Peng Wu (Science of The Total Environment, 2024)

A critical review of Mnammox coupled with the NDMO for innovative nitrogen removal - Xurui Zhu; Xiaonong Zhang; Bo Gao; Luomiao Ji; Rui Zhao; Peng Wu (Science of The Total Environment, 2024)

A method for accurate extraction of three-dimensional point cloud feature data in loading test of container ships - Rui Li; Hexin Wan; Ji Wang; Shilin Huo; C. Guedes Soares (Ocean Engineering, 2024)

A novel 4-DOF marine stern bearing support model considering discrete distribution effects - Ziqi Chen; Ji Wang; Rui Li; Yujun Liu (Ocean Engineering, 2024)

Toxicity prediction and risk assessment of per- and polyfluoroalkyl substances for threatened and endangered fishes - Yuanpu Ji; Xiaolei Wang; Rui Wang; Jiayu Wang; Xiaoli Zhao; Fengchang Wu (Environmental Pollution, 2024)

Straw return can increase maize yield by regulating soil bacteria and improving soil properties in arid and semi-arid areas - Xiaoling Wang; Rui Qian; Yafang Han; Zhe Ji; Qingxuan Yang; Longlong Wang; Xiaoli Chen; Kun Ma; Kadambot H.M. Siddique; Zhikuan Jia; Xiaolong Ren (European Journal of Agronomy, 2024)

Metasedimentary “carbon filter” and its implication for subduction zone carbon recycling - Ji-Lei Li; E.M. Stewart; Timm John; Jay J. Ague; Zhong-Rui Wang; Zhi-Pei Ma; Jun Gao (Earth and Planetary Science Letters, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

A critical review of impact and synergistic mechanisms of iron and co-elements in anammox - Bo Gao; Xiaonong Zhang; Xurui Zhu; Luomiao Ji; Rui Zhao; Peng Wu (Chemical Engineering Journal, 2024)

A critical review of comammox and synergistic nitrogen removal coupling anammox: Mechanisms and regulatory strategies - Da Jin; Xiaonong Zhang; Xingxing Zhang; Li Zhou; Zixuan Zhu; Ufoymungu Kisa Deogratias; Zhiqiang Wu; Kangyu Zhang; Xu Ji; Ting Ju; Xurui Zhu; Bo Gao; et al. (Science of The Total Environment, 2024)

Heavy metals and nutrients mediate the distribution of soil microbial community in a typical contaminated farmland of South China - Feng Zhang; Yunhe Xie; Rui Peng; Xionghui Ji; Lianyang Bai (Science of The Total Environment, 2024)

Enhanced photocatalytic Cr(VI) degradation and real-time detection using dual-fluorescent quantum dot-infused polysulfone microspheres - Rui Zhao; Feihong Hu; Shan Li; Chao Liu; Zhiwei Wang; Zhaoping Song; Dandan Ji; Xiaona Liu; Huili Wang; Wenxia Liu; Fengshan Zhang; Dehai Yu (Journal of Environmental Chemical Engineering, 2024)

Ultrasound-responsive ZnS:Ag QDs loaded TiO2 biointerfaces: In situ sonodynamic antimicrobial therapy for biomedical implants - Lei Ji; Yun Xue; Dong Wang; Yu Fan; You Zhou; Chuanan Shen; Rui Shi; Jiatao Zhang (Chemical Engineering Journal, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Advances in the Differentiation of hiPSCs into Cerebellar Neuronal Cells - Yingxin Wang; Wenzhu Liu; Yichang Jiao; Yitong Yang; Didi Shan; Xinbo Ji; Rui Zhang; Zexin Zhan; Yao Tang; Dandan Guo; Chuanzhu Yan; Fuchen Liu (Stem Cell Reviews and Reports, 2024)

Optimization of response surface methodology and in vitro antioxidant, antimicrobial activity of Phellodendron amurense callus tissue - Yuhong Zhang; YizhenSuo; Yanxin Jiang; Qiuyan Ji; Rui Fang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Iron Level in Pregnant Rats is Associated with Caries Susceptibility in Offsprings - Jun Lu; Shuaiqi Ji; Lei Ma; Yanhui Wang; Yongliang Wang; Jin Yue; Rui Han (Biological Trace Element Research, 2024)

Environmental pollution of paraben needs attention: A study of methylparaben and butylparaben co-exposure trigger neurobehavioral toxicity in zebrafish - Jing Xiang; Bing-Rui Lv; Ya-jun Shi; Wen-ming Chen; Ji-liang Zhang (Environmental Pollution, 2024)

Assessing the preservation of orbital signals across different sedimentary environments: Insights from stochastic sedimentation modeling - Meng Wang; Mingsong Li; Elizabeth A. Hajek; David B. Kemp; Yujing Wu; Hanyu Zhu; Chunju Huang; Haotian Zhang; Kaixuan Ji; Rui Zhang; Ren Wei; Zhijun Jin (Earth and Planetary Science Letters, 2024)

A newly isolated strain for poly(3-hydroxybutyrate) production under anaerobic conditions and the key enzyme analysis - Rui Ma; Ji Li; R.D. Tyagi; Xiaolei Zhang (Chemical Engineering Journal, 2024)

Role of regulating synthetic solvents in enhancing the catalytic performance of VPO catalysts for n-butane oxidation to maleic anhydride - Jiale Xu; Ning Li; Xiuyi Li; Renjie Ji; Xiaoyu Yan; Rui Huang; Chunyi Li (Chemical Engineering Journal, 2024)

Wearable hydrogel-based health monitoring systems: A new paradigm for health monitoring? - Xintao Wang; Haixia Ji; Li Gao; Rui Hao; Ying Shi; Junyan Yang; Yuan Hao; Jiahui Chen (Chemical Engineering Journal, 2024)

Four dodecanoic acid derivatives from the cold-seep-derived fungus Cladosporium cladosporioides 8-1 - Chang-Peng Li; Yin-Ping Song; Xiao-Rui Liang; Nai-Yun Ji (Natural Product Research, 2024)

MicroRNA-128-3p Affects Neuronal Apoptosis and Neurobehavior in Cerebral Palsy Rats by Targeting E3 Ubiquitin-Linking Enzyme Smurf2 and Regulating YY1 Expression - Xiaoqi Nie; Rui Cheng; Pengfei Hao; Yuhong Guo; Gang Chen; Lei Ji; Lu Jia (Molecular Neurobiology, 2024)

Strong controlling effect of stress evolution on the 2022 Ms5.0 Honghe earthquake sequence - Ye Zhu; Wenjie Fan; Yingfeng Ji; Weiling Zhu; Lili Feng; Rui Qu (Tectonophysics, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

A novel, green, and environmentally friendly PBS/nano-CaCO3 hybrid membrane - Ming Jing; Yanhong Ji; Liuchun Zheng; Xi Liu; Zunbo Han; Jiayi Cai; Rui Bai; Benqiao He (Journal of Environmental Chemical Engineering, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Gas chromatography-mass spectrometry and non-targeted metabolomics analysis reveals the flavor and nutritional metabolic differences of cow's milk fermented by Lactiplantibacillus plantarum with different phenotypic - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Highly nanostructured and carboxylated wood aerogel-based adsorption membrane reconstructed by grafting of polyacrylic acid for efficient removal of heavy-metal ions - Wen He; Bairen Wei; Shuang Liang; Rui Wang; Qiulin Ji; Gangzheng Hu; Wenxuan Li; Lei He; Juan Yu; Hongfei Zhu; Kaiyin Wang (Chemical Engineering Journal, 2024)

Diversity and environmental determinants of aquatic plants across China - Mengtian Ji; Rui Dong; Junhui Zhang; Xinlei Shi; Yuchao Wang; Qiqi Huang; Dan Qu; Yuyu Wang (Hydrobiologia, 2024)

Repetitive Transcranial Magnetic Stimulation-Mediated Neuroprotection in the 5xFAD Mouse Model of Alzheimer’s Disease Through GABRG2 and SNAP25 Modulation - Jinyang Wang; Chenming Zhou; Zhimin Huang; Xiaoming Ji; Rui Cui; Yunxiao Kang; Guoliang Zhang; Yu Wang; Tianyun Zhang (Molecular Neurobiology, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Separation, enrichment and cytoprotection of antioxidant peptides from Xuanwei ham using aqueous two-phase extraction - Rui-hong Xie; Shan Xiao; Xuan Chen; Bo Wang; Yao-yao Hu; Ji-hui Wang (Food Chemistry, 2024)

Efficient nitrogen removal from mainstream sewage in tidal flow constructed wetlands: Targeted migration and conducive spatial distribution for pollutants removal - Rui Ma; Caocong Liu; Yiyuan Zhuo; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2024)

Cytokines-activated nuclear IKKα-FAT10 pathway induces breast cancer tamoxifen-resistance - Xueyan Chen; Weilin Wu; Ji-Hak Jeong; Matjaz Rokavec; Rui Wei; Shaolong Feng; Werner Schroth; Hiltrud Brauch; Shangwei Zhong; Jun-Li Luo (Science China Life Sciences, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Modern pollen-vegetation relationships along altitudinal vegetation belts in the Leigong Mountain of southwestern China - Shuming Li; Wenwei Zhao; Lisi Wei; Weihe Ren; Qinran Gu; Siqi Wu; Yang Ji; Ziteng Yang; Rui Zhuang; Chunzhu Chen (Journal of Mountain Science, 2024)

Bioactivities of essential oil extracted from Elsholtzia densa Benth. And its main components against Tribolium castaneum eggs and pupae - Xiaohan Zhang; Rui Feng; Yufei Tang; Weibao Kong; Ji Zhang; Junyu Liang (Pesticide Biochemistry and Physiology, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Lotus pollen-derived nitrogen and phosphorus self-doped TiO2/carbon materials for photoelectrochemical application - Rui Chen; Ying-Ying Wang; Xia Jiang; Ming-Hao Ji; Ke-Xian Li; Hao-Yan Shi; Hai-Long Wang; Yan-Xin Chen; Can-Zhong Lu (Journal of Environmental Chemical Engineering, 2024)

A lychee fermentate with enriched acetate but lowered GABA attenuates DSS-induced colitis by reinforcing gut barrier function and modulating intestinal microbiota - Rui Huang; Hong Yao; Suying Ji; Junfeng Wu; Qingran Lin; Tanushree B. Gupta; Dan Gan; Xiyang Wu (Food Bioscience, 2024)

Unraveling umami complexity: From exploring umami peptides in fermented soybean curd to molecular elucidation of taste mechanisms - Yong Dong; Rui Chang; Zhongwei Ji; Yuezheng Xu; Qingxi Ren; Zhilei Zhou; Jian Mao (Food Bioscience, 2024)

Low temperature catalytic activity of molybdenum promoted two-dimensional boron nitride in propane oxidative dehydrogenation reaction - Yixiang Zhu; Rui Chen; Yixuan Yang; Yu Liu; Xuyu Wang; Hongbing Ji (Chemical Engineering Journal, 2024)

Temperature-driven dynamic evolution process of Ag species on silver-loaded Zr0.2Sn0.8O2 catalyst for selective catalytic oxidation of ammonia - Yan Zhang; Zongxiang Yang; Meng Wang; Min Zhang; Caixia Liu; Qingling Liu; Weichao Wang; Ziyin Zhang; Rui Han; Na Ji (Chemical Engineering Journal, 2024)

Impacts of permafrost degradation on streamflow in the northern Himalayas - Linfeng Fan; Fang Ji; Xingxing Kuang; Zhilin Guo; Rui Zhang; Chunmiao Zheng (Science China Earth Sciences, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

Encapsulate Co3O4 within ultrathin graphene sheets to enhance peroxymonosulfate activation by tuning surface electronic structures - Taobo Huang; Rui An; Jie Li; Wen Liu; Xiuping Zhu; Haodong Ji; Ting Wang (Science of The Total Environment, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Snakehead vesiculovirus (SHVV) leader RNA interacts with host antiviral factors RPS8 and L13a and promotes virus replication - Yan Ji; Rui Cheng; Xuan Zhou; Jiaqi Zhang; Xiaodan Liu; Suhong Sheng; Chi Zhang (Fish & Shellfish Immunology, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Insights into the Degradation and Mechanism of the Enhanced Persulfate Degradation of Tetracycline using an Efficient 3D Copper Metal–Organic Frameworks - Rui Zhou; Congyang Zou; Yong Wang; Zhuyou Zhou; Menghe Liu; Yufeng Ji (Water, Air, & Soil Pollution, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Rapid immobilization of arsenic in contaminated soils by microwave irradiation combined with magnetic biochar: Microwave-induced electron transfer for oxidation and immobilization of arsenic (III) - Dengcai Zhang; Junhao Lin; Juan Luo; Shichang Sun; Xi Zhang; Rui Ma; Juan Peng; Fei Ji; Shuaifei Zheng; Zhen Tian; Ning Ma (Science of The Total Environment, 2024)

Experimental investigation of propeller blade back cavitation induced pressure pulses by synchronous observation - Rui Wu; Heng Liu; Weiqi Chen; Sheng Ji; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Medical waste incineration fly ash-based magnesium potassium phosphate cement: Calcium-reinforced chlorine solidification/stabilization mechanism and optimized carbon reduction process strategy - Runjie Liu; Shiwei Liu; Shichang Sun; Xing Cao; Junhao Lin; Juan Peng; Fei Ji; Rui Ma (Journal of Environmental Management, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effect of berry-derived phenolic products on blood lipid profiles: A systematic review and meta-analysis - Chunxiao Ji; Rui Wang; Dongliang Wang; Yongle Luo; Zaiming Huang; Jianying Liu; Anwei Cheng (Food Bioscience, 2024)

Modeling investigation of wave-induced longshore current distribution patterns on barred beaches - Chao Ji; Qinghe Zhang; Tongqing Chen; Dianguang Ma; Rui Huang (Estuarine, Coastal and Shelf Science, 2024)

Global Sensitivity Analysis of Crop Parameters Based on AquaCrop Model - Wei Li; Rui Song; Muhammad Awais; Leilei Ji; Shuo Li; Mingjiang Liu; Tao Lang; Handong Qi (Water Resources Management, 2024)

A triggered DNA nanomachine with enzyme-free for the rapid detection of telomerase activity in a one-step method - Huajie Pang; Yanan Peng; Rui Zhang; Zhijun Gao; Xiangde Lai; Dongxia Li; Xuan Zhao; Yuanyuan Wang; Hua Pei; Bin Qiao; Yuxiang Ji; Qiang Wu (Analytica Chimica Acta, 2024)

Salinity as a key factor affecting viral activity and life strategies in alpine lakes - Lin Zang; Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Xuanying Song; Yunlan Yang; Lanlan Cai; Keshao Liu; Guannan Mao; Mukan Ji; Rui Zhang (Limnology and Oceanography, 2024)
Viruses are major players in the biosphere, yet little is known about their dynamics and life strategies in alpine lakes, particularly those on the Tibetan Plateau. We investigated microbial abundance, viral dynamics, and viral life strategies in 10 high‐altitude Tibetan lakes and found that they harbor high levels of active viruses. Salinity was identified as a crucial factor influencing viral abundance, dynamics, as well as viral life strategies. Lytic and lysogenic viral productions in moderate‐ and high‐salinity lakes were significantly higher than those in freshwater lakes. A trade‐off between viral life strategies resulted in a switch from lysis to lysogeny in high‐salinity lakes. Virus‐mediated cell lysis and virus decay in sampled Tibetan lakes could release about 162.72 and 2.84 μ g C L −1 d −1 , respectively. These findings revealed the crucial role of viruses in the carbon cycle of Tibetan lakes, and a switch in viral life strategies may impact their contribution to the carbon cycle. The potential impact of salinity changes triggered by climate change on the carbon cycle in alpine lakes worldwide is highlighted.

Numerical calculation of overlapping line heating for marine titanium alloy curved plate - Shun Wang; Jiayan Wang; Zhikang Xu; Ji Wang; Rui Li (Ocean Engineering, 2024)

Effects of κ-carrageenan on the emulsifying ability and encapsulation properties of pea protein isolate-grape seed oil emulsions - Wenjuan Wang; Rui Sun; Suping Ji; Qiang Xia (Food Chemistry, 2024)

Modulation of charge distribution enabling CuNi nano-alloys for efficient ammonia oxidation reaction to nitrite production - Zixian Mao; Yunrui Tian; Baitong Guo; Rui Chen; Ye Zeng; Feng Hou; Xiao Yan; Ji Liang (Chemical Engineering Journal, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

RNAi-mediated plant sterol modification to control insect herbivore pests: insights from Arabidopsis and the diamondback moth - Ivy W. Chen; Robert J. Grebenok; Cheng Zhao; Li He; Jiaxin Lei; Rui Ji; Nicolo Hernandez; Joshua S. Yuan; Hisashi Koiwa; Spencer T. Behmer; Keyan Zhu-Salzman (Journal of Pest Science, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Ubiquitination-dependent protein homeostasis is critical for the thermotolerance of the economically valuable seaweed Pyropia haitanensis - Rui Zhao; Jian Wen; Kai Xu; Yan Xu; Dehua Ji; Chaotian Xie; Wenlei Wang (Aquaculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Path following of QAUV using attitude-velocity coupling model - Daxiong Ji; Rui Wang (Ocean Engineering, 2024)

Excitation force on a pump-jet propeller: The clocking effect of pre-swirl stator - Yu Zhang; Jieting Han; Sheng Ji; Rui Wu; Bin Huang; Dahai Zhang; Dazhuan Wu (Ocean Engineering, 2024)

Surface sediment erosion characteristics and influencing factors in the subaqueous delta of the abandoned Yellow River Estuary - Chaoran Lin; Rui Bao; Longhai Zhu; Rijun Hu; Jinlong Ji; Shilei Yu (Marine Geology, 2024)

Numerical investigation on the spray characteristics of biodiesel with gas-assisted atomization injection - Rui Liu; Lingfeng Zhong; Songhong Li; Jing Li; Haocheng Ji (Fuel, 2024)

Shaking table test and numerical simulation of a precast frame-shear wall structure with innovative untopped precast concrete floors - Rui Pang; Yuan-yuan Sun; Zhu Xu; Ke Xu; Jing Cui; Long-ji Dang (Engineering Structures, 2024)

Grazing reduced greenhouse gas fluxes in Inner Mongolia grasslands: A meta-analysis - Peidong Yu; Hasbagan Ganjurjav; Guozheng Hu; Mingjie Li; Zhiqiang Wan; Guoxu Ji; Rui Gu; Qingzhu Gao (Ecological Engineering, 2024)

GABRP Promotes the Metastasis of Pancreatic Cancer by Activation of the MEK/ERK Signaling Pathway - Yong Meng; Rui Li; Shuaiming Geng; Wenhao Chen; Weirong Jiang; Zhiwen Li; Ji Hao; Zhen Xu (Biochemical Genetics, 2024)

Deformation Intelligent Prediction of Titanium Alloy Plate Forming Based on BP Neural Network and Sparrow Search Algorithm - Shun Wang; Jiayan Wang; Zhikang Xu; Ji Wang; Rui Li; Jinliang Dai (Journal of Marine Science and Engineering, 2024)
The application of titanium alloy in shipbuilding can reduce ship weight and carbon emissions. To solve the problem of titanium alloy forming, the deformation prediction of titanium alloy line heating based on a backpropagation (BP) neural network and sparrow search algorithm (SSA) was researched. Based on the thermal–elastic–plastic finite element method, the numerical calculation model of TA5 titanium alloy overlapping heating forming was established. The feasibility of the model was verified by comparing it with the numerical calculation and experiment of low-carbon steel. Considering the characteristics of the titanium alloy-forming process, 73 groups of titanium alloy-forming schemes were obtained by the Latin hypercube sampling method. The deformation data of the samples were obtained by using the numerical calculation model of titanium alloy forming. The prediction methods of titanium alloy-forming deformation based on BP, genetic algorithm–backpropagation (GA-BP), and SSA-BP were proposed. The accuracy of different neural network prediction models was analyzed. The mean absolute percentage errors (MAPEs) of BP, GA-BP, and SSA-BP in shrinkage prediction were 7.45%, 4.08%, and 2.96%, respectively. The MAPEs of BP, GA-BP, and SSA-BP in deflection prediction were 8.44%, 4.73%, and 2.64%, respectively. The goodness of fit (R2) of SSA-BP is closest to 1 among the three models. The calculation results show that SSA-BP is better than BP and GA-BP in predicting the forming deformation of titanium alloy. The maximum prediction error of SSA-BP is 4.95%, which is within the allowable range of engineering error. The SSA-BP prediction model is suitable for the rapid and accurate prediction of the deformation of titanium alloy line heating forming. The intelligent prediction model provides data support for intelligent decisions for titanium alloy forming.

Super Resolution Mapping of Scatterometer Ocean Surface Wind Speed Using Generative Adversarial Network: Experiments in the Southern China Sea - Xianci Wan; Baojian Liu; Zhizhou Guo; Zhenghuan Xia; Tao Zhang; Rui Ji; Wei Wan (Journal of Marine Science and Engineering, 2024)
This paper designed a Generative Adversarial Network (GAN)-based super-resolution framework for scatterometer ocean surface wind speed (OSWS) mapping. An improved GAN, WSGAN, was well-trained to generate high-resolution OSWS (~1/64 km) from low-resolution OSWS (~12.5 km) retrieved from scatterometer observations. The generator of GAN incorporated Synthetic Aperture Radar (SAR) information in the training phase. Therefore, the pre-trained model could reconstruct high-resolution OSWS with historical local spatial and texture information. The training experiments were executed in the South China Sea using the OSWS generated from the Advanced SCATterometer (ASCAT) scatterometer and Sentinel-1 SAR OSWS set. Several GAN-based methods were compared, and WSGAN performed the best in most sea states, enabling more detail mining with fewer checkerboard artifacts at a scale factor of eight. The model reaches an overall root mean square error (RMSE) of 0.81 m/s and an overall mean absolute error (MAE) of 0.68 m/s in the collocation region of ASCAT and Sentinel-1. The model also exhibits excellent generalization capability in another scatterometer with an overall RMSE of 1.11 m/s. This study benefits high-resolution OSWS users when no SAR observation is available.

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

Effects of Lacticaseibacillus paracasei SNB-derived postbiotic components on intestinal barrier dysfunction and composition of gut microbiota - Luyao Xiao; Changliang Zhang; Xueliang Zhang; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Research International, 2024)

Synthesis of amorphous-MnO2/Clinoptilolite and its utilization for NH4+-N oxidation in an anoxic environment - Caocong Liu; Yiyuan Zhuo; Yuzhe Chen; Yuanxiang Mao; Qiushi Shen; Jiangsen Ma; Rui Ma; Linsong Cheng; Fangying Ji; Xiaoyi Xu (Environmental Research, 2024)

Carbon dioxide and methane as carbon source for the production of polyhydroxyalkanoates and concomitant carbon fixation - Rui Ma; Ji Li; RD Tyagi; Xiaolei Zhang (Bioresource Technology, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

New insight into the pyrophoricity and mechanism of ironic sulfide from synergistic effect of FeS and FeS2 - Kai Pan; Hui Liu; Zhihui Lang; Rui Huang; Ze Wei; Wenjing Ji; Jianhai Wang; Dong Ye; Haining Wang (Fuel, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

The interaction among Kluyveromyces marxianus G-Y4, Lacticaseibacillus paracasei GL1, and Lactobacillus helveticus SNA12 and signaling molecule AI-2 participate in the formation of biofilm - Xiaomeng Wang; Kai Ma; Changliang Zhang; Feng Ji; Lili Chen; Xueliang Zhang; Ghahvechi Chaeipeima Mahsa; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Microbiology, 2023)

A review of starch swelling behavior: Its mechanism, determination methods, influencing factors, and influence on food quality - Ruoyu Jia; Congli Cui; Lin Gao; Yang Qin; Na Ji; Lei Dai; Yanfei Wang; Liu Xiong; Rui Shi; Qingjie Sun (Carbohydrate Polymers, 2023)

Calibration of the carbonate clumped isotope thermometer of land snail shells - Rui Bao; Xuefen Sheng; Chenglong Li; Can Cui; Hao Yan; Junfeng Ji; Jun Chen (Chemical Geology, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

A Pre-Procession Module for Point-Based Deep Learning in Dense Point Clouds in the Ship Engineering Field - Shilin Huo; Yujun Liu; Ji Wang; Rui Li; Xiao Liu; Jiawei Shi (Journal of Marine Science and Engineering, 2023)
Recently, point cloud technology has been applied in the ship engineering field. However, the dense point cloud acquired by terrestrial laser scanning (TLS) technology in ship engineering applications brings an obstacle to some powerful and advanced point-based deep learning point cloud processing methods. This paper presents a deep learning pre-procession module to ensure the feasibility of processing dense point clouds on commonly available computer devices. The pre-procession module is designed according to the traditional point cloud processing methods and the PointNet++ paradigm, and is evaluated on two ship structure datasets and two popular point cloud datasets. Experimental results illustrate that (i) the proposed module improves the performance of point-based deep learning semantic segmentation networks, and (ii) the proposed module empowers the existing point-based deep learning networks with the capability to process dense input point clouds. The proposed module may provide a useful semantic segmentation tool for realistic dense point clouds in various industrial applications.

Regional differences, dynamic evolution, and spatial spillover effects of carbon emission intensity in urban agglomerations - Rui Qiao; Feng Dong; Xiaoqian Xie; Rui Ji (Environmental Science and Pollution Research, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Enhanced As extraction from paddy soils with high As contamination risk by rice plant upon Si fertilization - Rui Huang; Xin Wang; Wei Wei; Yunhe Xie; Saihua Liu; Haoyu Chen; Renjie Zhang; Xionghui Ji (Chemosphere, 2023)

Developmental and neurobehavioral toxicity of 2,2′-methylenebis(6-tert-butyl-4-methylphenol) (antioxidant AO2246) during the early life stage of zebrafish - Yinan Chai; Donglai Sheng; Xiaowei Ji; Yanlong Meng; Feihao Shen; Rui He; Runjia Ma; Yuying Wang (Science of The Total Environment, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Photocatalysis-Fenton mechanism of rGO-enhanced Fe-doped carbon nitride with boosted degradation performance towards rhodamine B - Fuwang Zhao; Yanling Yang; Siyang Ji; Rui Yu; Xing Li; Zhiwei Zhou (Journal of Water Process Engineering, 2023)

Optimizing teleconsultation scheduling to make healthcare greener - Yan Qiao; Yunkai Zhai; Rui Ma; Menglei Ji; Wei Lu (Journal of Cleaner Production, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Effects of Lactiplantibacillus plantarum with different phenotypic features on the nutrition, flavor, gel properties, and digestion of fermented soymilk - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Suying Wang; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2023)

Establishment of CRISPR-Cpf1-assisted gene editing tool and engineering of 4-hydroxyisoleucine biosynthesis in Corynebacterium glutamicum - Rui Chen; Feng Shi; Youhe Xiang; Wenmei Lai; Guohui Ji (World Journal of Microbiology and Biotechnology, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Impact of nitrogen addition on single and mixed tree leaf litter decomposition depends on N forms in subtropical China - Pan-Pan Wu; Zao Zhang; Rui Li; Jing-Hao Ji; Rong Mao (Applied Soil Ecology, 2023)

Mn(VII) enhanced by CaSO3 to remove trace organic pollutants in high salt organic wastewater: Further enhancement of salinity - Linsong Cheng; Yuanxiang Mao; Lei Jiang; Rui Ma; Jiangsen Ma; Yiyuan Zhuo; Qiushi Shen; Caocong Liu; Liuwei Zhao; Xiaoyi Xu; Fangying Ji (Chemosphere, 2023)

Preparation of magnesium potassium phosphate cement from municipal solid waste incineration fly ash and lead slag co-blended: Ca-induced crystal reconstruction process and Pb-Cl synergistic solidification mechanism - Shiwei Liu; Xing Cao; Weichen Yang; Runjie Liu; Lin Fang; Rui Ma; Juan Peng; Shuaifei Zheng; Fei Ji (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Research on rice leaf area index estimation based on fusion of texture and spectral information - Wangshu Yuan; Ying Meng; Yan Li; Zeguang Ji; Qingming Kong; Rui Gao; Zhongbin Su (Computers and Electronics in Agriculture, 2023)

Holocene climatic controls on flooding regime along the Ussuri River in Northeast Asia - Zhenqing Zhang; Lin Li; Rui Yin; Lu Zhang; Kai Yi; He Ji; Haijiao Yin; Lili Huo (Science of The Total Environment, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Preparation, characterization, and evaluation of tamarind seed polysaccharide-carboxymethylcellulose buccal films loaded with soybean peptides-chitosan nanoparticles - Suping Ji; Rui Sun; Wenjuan Wang; Qiang Xia (Food Hydrocolloids, 2023)

The first homosporous lycophyte genome revealed the association between the recent dynamic accumulation of LTR-RTs and genome size variation - Ji-Gao Yu; Jun-Yong Tang; Ran Wei; Mei-Fang Lan; Rui-Chen Xiang; Xian-Chun Zhang; Qiao-Ping Xiang (Plant Molecular Biology, 2023)

Degradation of trichloroethylene by double dielectric barrier discharge (DDBD) plasma technology: Performance, product analysis and acute biotoxicity assessment - Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Er-Hong Duan; Meng-Fei Han; Hsing-Cheng Hsi; Ji-Guang Deng (Chemosphere, 2023)

SEDLNet: An unsupervised precise lightweight extraction method for farmland areas - Zeguang Ji; Junshuo Wei; Xi Chen; Wangshu Yuan; Qingming Kong; Rui Gao; Zhongbin Su (Computers and Electronics in Agriculture, 2023)

Government–business relations, environmental information transparency, and Hu-line-related factors in China - Rui Yang; Yingwen Chen; Yiqun Liu; Yuchen Feng; Jianwan Ji; Christina W. Y. Wong; Xin Miao; Yanhong Tang (Environment, Development and Sustainability, 2023)

Study on the Methods of Measurement, Optimization and Forecast of Propulsion Shaft Bearing Load of Ships - Rui Li; Ji Wang; Ziqi Chen; Feixiang Wang; Yujun Liu (Journal of Marine Science and Engineering, 2023)
The qualit12y of shafting alignment is related to the reliability and safety of a ship’s operation, and bearing displacement adjustment (BDA) plays a key role in shafting alignment. To solve the problems encountered in ship shafting alignment in the actual construction, this study focused on the investigation of the shafting load measurement system based on the strain gauge method (SGM), used the optimization method based on quadratic programming (QP) to calculate the BDA and adopted algorithms based on the bearing load influence coefficients (BICs) to forecast the load after the adjustment. The experimental work, as well as the measurement, calculation and analysis of several real ships, indicated that the measurement, optimization and forecasting methods of the bearing load of the propulsion shafting of large ships in this study would be significant for guiding the actual construction work of ship shafting alignment.

Emerging poly- and perfluoroalkyl substances in water and sediment from Qiantang River-Hangzhou Bay - Haixiang Cheng; Hangbiao Jin; Bin Lu; Chenhan Lv; Yinghui Ji; Hui Zhang; Rui Fan; Nan Zhao (Science of The Total Environment, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Subassembly Partition of Hull Block Based on Two-Dimensional PSO Algorithm - Bo Liu; Rui Li; Ji Wang; Yujun Liu; Sheng Li (Journal of Marine Science and Engineering, 2023)
Subassembly partition is an important process in hull block building as it greatly affects the efficiency and quality of the assembly work. Recently, an experience-based method has been widely applied to the subassembly partition process, which consumes much design time and manpower, thus causing more challenges toward a more highly automated and efficient stage in this process. To shorten the gap, an automated subassembly partition method is presented in this study. First, the assembly information model is defined with essential attributes and topological relations of the parts. Second, an optimization model is established with consideration of a trade-off between the intra-cluster cohesion and cluster number on the premise of satisfying certain constraints. After that, considering the fuzziness and diversity of the subassembly partition problem, a two-dimensional coding discrete particle swarm optimization (PSO) algorithm is developed. Finally, two blocks are demonstrated as instances to verify the proposed method, and the results show that the proposed method is feasible and applicable to the block with a flat structure.

Hormesis effects of sulfoxaflor on Aphis gossypii feeding, growth, reproduction behaviour and the related mechanisms - Li Wang; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Weiling Huang; Changhui Rui; Li Cui (Science of The Total Environment, 2023)

High magnesian schist, granitic gneiss, amphibolite and monzogneiss in the eastern Ama Drime Massif in South Tibet (China): A rifted Paleoproterozoic arc fringed the western Columbia supercontinent? - Rui Li; Wenjiao Xiao; Qigui Mao; Ji'en Zhang; Songjian Ao; Dongfang Song; Zhou Tan; Hao Wang; Saunak Bhandari (Precambrian Research, 2023)

Structural incorporation of iron influences biomethylation potential of mercury sulfide - Yunyun Ji; Shan Gao; Rui Si; Zhanhua Zhang; Li Tian; Wenyu Guan; Weichao Wang; Jiubin Chen; Wei Chen; Pedro J.J. Alvarez; Tong Zhang (Geochimica et Cosmochimica Acta, 2023)

Mechanistic studies of polyphenols reducing the trypsin inhibitory activity of ovomucoid: Structure, conformation, and interactions - Rui Cui; Shengnan Ji; Minquan Xia; Xing Fu; Xi Huang (Food Chemistry, 2023)

Preparation and characterization of V-type starch nanoparticles by an oil-water interface method - Hao Lu; Xiaoyang He; Yang Qin; Na Ji; Lei Dai; Liu Xiong; Rui Shi; Tao Wang; Qingjie Sun (Food Hydrocolloids, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Sulfoxaflor adversely influences the biological characteristics of Coccinella septempunctata by suppressing vitellogenin expression and predation activity - Li Wang; Yanhui Zhai; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Huizhu Yuan; Changhui Rui; Li Cui (Journal of Hazardous Materials, 2023)

Boosted degradation of tetracycline over a novel hierarchical 2D/1D S-scheme heterojunction Bi2O4 @SnS under visible light irradiation - Shenggeng Zhao; Fangyan Chen; Yanhua Song; Ji Hua; Rui Wu; Jietong Yang; Yubin Tang (Journal of Environmental Chemical Engineering, 2023)

Fabrication of starch-based emulsion gel beads by an inverse gelation technique for loading proanthocyanidin and curcumin - Xiaotong Bu; Minghang Guan; Lei Dai; Na Ji; Yang Qin; Xingfeng Xu; Liu Xiong; Rui Shi; Qingjie Sun (Food Hydrocolloids, 2023)

Long-term performance analysis of BDS-3 precise point positioning (PPP-B2b) service - Shuang Sun; Min Wang; Changjian Liu; Xin Meng; Rui Ji (GPS Solutions, 2023)

Characteristics, sources and health risk assessment of atmospheric carbonyls during multiple ozone pollution episodes in urban Beijing: Insights into control strategies - Yunfeng Li; Hong Li; Xin Zhang; Yuanyuan Ji; Rui Gao; Zhenhai Wu; Manfei Yin; Lei Nie; Wei Wei; Guohao Li; Yafei Wang; Mei Luo; et al. (Science of The Total Environment, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Upcycling corn straw into nanocelluloses via enzyme-assisted homogenization: Application as building blocks for high-performance films - Hongbin Yang; Long Bai; Yaxin Duan; Hongxiang Xie; Xumei Wang; Rui Zhang; Xingxiang Ji; Chuanling Si (Journal of Cleaner Production, 2023)

Subduction hydrothermal regime and seismotectonic variation along Kermadec–Tonga megathrusts - Ye Zhu; Yingfeng Ji; Weiling Zhu; Rui Qu; Chaodi Xie; Deng Zeng (Journal of Asian Earth Sciences, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Phytoplankton biomass dynamics with diffuse terrestrial nutrients pollution discharge into bay - Wei Ouyang; Rui Wang; Kaiyue Ji; Xitao Liu; Fang Geng; Xin Hao; Chunye Lin (Chemosphere, 2023)

The physicochemical properties of a starch–sodium stearoyl lactylate complex formed via annealing treatment in ethanol solutions - Xiaoyu Chen; Chaofan Wang; Xiaoyang He; Yang Qin; Lei Dai; Liu Xiong; Tao Wang; Rui Shi; Na Ji; Qingjie Sun (Food Hydrocolloids, 2023)

Efficient removal of nitrogen from tidal flow constructed wetlands based on the in-situ zeolite regeneration: Measures and mechanisms - Rui Ma; Jiangsen Ma; Yuzhe Chen; Yiyuan Zhuo; Linsong Cheng; Lei Jiang; Yuanxiang Mao; Qiushi Shen; Caocun Liu; Fangying Ji (Chemical Engineering Journal, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Investigation of lake shrinkage attributed to climate change over the past 33 years in Inner Mongolia, China - Yanfei Zhang; Zilong Liao; Xiaomin Xu; Wentao Liang; Zhenhua Han; Gang Ji; Rui Jiao (Climatic Change, 2023)

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

Study on the trajectory of tip leakage vortex and energy characteristics of mixed-flow pump under cavitation conditions - Wei Li; Mingjiang Liu; Leilei Ji; Shuo Li; Rui Song; Cheng Wang; Weidong Cao; Ramesh K. Agarwal (Ocean Engineering, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Surrogacy of bird species in systematic conservation planning and conservation assessments in Yunnan Province, China - Jian Zhou; Fei-ling Yang; Zi-jie Zhong; Ji Zhang; Xian Leng; Jin Ye; Rui-dong Wu (Journal of Mountain Science, 2022)

Acacetin antagonized lipotoxicity in pancreatic β-cells via ameliorating oxidative stress and endoplasmic reticulum stress - Ning Wang; Qing Gao; Jie Shi; Chen Yulan; Weimeng Ji; Xiumei Sheng; Rui Zhang (Molecular Biology Reports, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Expression Quantitative Trait Locus rs6356 Is Associated with Susceptibility to Heroin Addiction by Potentially Influencing TH Gene Expression in the Hippocampus and Nucleus Accumbens - Kena Wang; Hongbo Zhang; Jinshan Ji; Rui Zhang; Wei Dang; Qiaoli Xie; Yongsheng Zhu; Jianbo Zhang (Journal of Molecular Neuroscience, 2022)

Transcriptomic Analysis of Circulating Neutrophils in Sheep with Mineral Element Imbalance - Di Wang; Ming Ji; Qijun Zhou; Chengyuan Su; Shuai Lian; Jianfa Wang; Jiasan Zheng; Rui Wu (Biological Trace Element Research, 2022)

Comparison of separated and combined photodegradation and biofiltration technology for the treatment of volatile organic compounds: A critical review - Meng-Fei Han; Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Zhuo-Wei Cheng; Ke Feng; Miao-Miao Qu; Jian-Meng Chen; Ji-Guang Deng; Hsing-Cheng Hsi (Critical Reviews in Environmental Science and Technology, 2022)

Influence of combined exposure levels of total arsenic and inorganic arsenic on arsenic methylation capacity among university students: findings from Bayesian kernel machine regression analysis - Rui Jiang; Qing Zhang; Dongmei Ji; Tingting Jiang; Yuan Hu; Shitao He; Long Tao; Juan Shen; Wei Zhang; Yuxiang Song; Yicheng Ma; Shilu Tong; et al. (Environmental Science and Pollution Research, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

A two-phase comprehensive NSCLC prognostic study identifies lncRNAs with significant main effect and interaction - Jing Zhu; Jinxing Guan; Xinyu Ji; Yunjie Song; Xiaoshuang Xu; Qianqian Wang; Quanan Zhang; Renhua Guo; Rui Wang; Ruyang Zhang (Molecular Genetics and Genomics, 2022)
Long noncoding RNA (lncRNA) are involved in regulating physiological behaviors for various malignant tumors, including non-small-cell lung cancer (NSCLC). However, few studies comprehensively evaluated both lncRNA–lncRNA interaction effects and main effects of lncRNA on overall survival of NSCLC. Hence, we performed a two-phase designed study of lncRNA expression in tumor tissues using 604 NSCLC patients from The Cancer Genome Atlas as the discovery phase and 839 patients from Gene Expression Omnibus as the validation phase. In the discovery phase, we adopted a two-step strategy, Screening before Testing , for dimension reduction and signal detection. These candidate lncRNAs first screened out by the weighted random forest (Ranger), were then tested through the Cox proportional hazards model adjusted for covariates. Significant lncRNAs with either type of effects aforementioned were carried forward into the validation phase to confirm their significances again. As a result, in the discovery phase, 19 lncRNAs were identified by Ranger, among which five lncRNAs and one pair of lncRNA–lncRNA interaction exhibited significant effects (FDR- q ≤ 0.05) main and interaction effects on NSCLC survival, respectively, through Cox model. After the independent validation, we finally observed that one lncRNA (ENSG00000227403.1) with main effect was robustly associated with NSCLC prognosis ( HR discovery = 0.90, P = 1.20 × 10 –3 ; HR validation = 0.94, P = 4.11 × 10 –3 ) and one pair of lncRNAs (ENSG00000267121.4 and ENSG00000272369.1) had significant interaction effect on NSCLC survival ( HR discovery = 1.12, P = 3.07 × 10 –4 ; HR validation = 1.11, P = 0.0397). Our comprehensive NSCLC prognostic study of lncRNA provided population-level evidence for further functional study.

Evaluation of leachate production and level in municipal solid waste landfills considering secondary compression - Han Ke; Chen Sheng Zhang; Jie Hu; Rui Qin; Yun Min Chen; Ji Wu Lan (Environmental Science and Pollution Research, 2022)

Expression of Human Uncoupling Protein-1 in Escherichia coli Decreases its Survival Under Extremely Acidic Conditions - Rui Tang; Wei Sun; Ji-Chun Zhang; Liufeng Mao; Natalie Quanquin; Donghai Wu; Yirong Sun (Current Microbiology, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Mutual impacts and interactions of antibiotic resistance genes, microcystin synthetase genes, graphene oxide, and Microcystis aeruginosa in synthetic wastewater - Shichao Wu; Xiyan Ji; Xin Li; Jing Ye; Wenwu Xu; Rui Wang; Meifang Hou (Environmental Science and Pollution Research, 2022)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Late Silurian to early Devonian development of the Chingiz accretion arc, West Junggar: insights into accretion arc evolution in the Central Asia Orogenic Belt - Yichao Chen; Ji’En Zhang; Wenjiao Xiao; Renjie Zhou; Shuaihua Song; Zhiyong Zhang; Songjian Ao; Miao Sang; Qian W.L. Zhang; Rui Li; Zhen M.G. Li; Yin Liu; et al. (International Geology Review, 2021)

The Water Resisting Properties of the Top Portion of the Ordovician Limestone Aquifer in the North China Coalfield - Hao Wang; Shuning Dong; Rui Chai; Wei Qiao; Jian Yang; Ji Liu; Linsheng Zhou; Zhenfang Zhou; Zhaoxing Liu; Hongbo Shang (Mine Water and the Environment, 2021)

Oxiracetam Mediates Neuroprotection Through the Regulation of Microglia Under Hypoxia-Ischemia Neonatal Brain Injury in Mice - Dan Wang; Yanbang Wei; Jingxia Tian; Dong He; Rui Zhang; Xiaoshuai Ji; Xiaoming Huang; Jun Sun; Jiajia Gao; Zixiao Wang; Qi Pang; Qian Liu (Molecular Neurobiology, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Seasonal variations of water quality response to land use metrics at multi-spatial scales in the Yangtze River basin - Jiahui Xu; Rui Liu; Maofei Ni; Jing Zhang; Qin Ji; Zuolin Xiao (Environmental Science and Pollution Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Cracking behaviors and strength of rock-like samples with steps of different geometries under shear stress - Hui-lin Le; Ji-hong Wei; Shao-rui Sun; Chu-chu Zhang (Journal of Mountain Science, 2021)

Transcriptome profiling analysis of two contrasting barley genotypes in general combining ability for yield traits - Xiaodong Chen; Bin Zhao; Changhao Ji; Bin Zhu; Rui Wang (Brazilian Journal of Botany, 2021)

The circular RNAs differential expression profiles in the metastasis of salivary adenoid cystic carcinoma cells - Rui Ju; Yanling Huang; Zeyou Guo; Lu Han; Suhui Ji; Luyang Zhao; Jie Long (Molecular and Cellular Biochemistry, 2021)

Dynamic Response of Phragmites australis and Suaeda salsa to Climate Change in the Liaohe Delta Wetland - Yushu Zhang; Wenying Yu; Ruipeng Ji; Yijun Zhao; Rui Feng; Qingyu Jia; Jinwen Wu (Journal of Meteorological Research, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Study on NOx removal from simulated flue gas by an electrobiofilm reactor: EDTA-ferrous regeneration and biological kinetics mechanism - Nan Liu; Ying-ying Li; Du-juan Ouyang; Rui Guo; Run Chen; Wei Li; Ji-xiang Li; Ji-hong Zhao (Environmental Science and Pollution Research, 2021)

Comparison of rapid freezing versus vitrification for human sperm cryopreservation using sucrose in closed straw systems - Huanhuan Hu; Guojie Ji; Xiaowei Shi; Rui Liu; Jing Zhang; Han Zhang; Xiaozheng Yuan; Guoyi Zhang; Wenzheng Yuan; Mingwen Li (Cell and Tissue Banking, 2020)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Erratum to: Transmission risk of patients with COVID-19 meeting discharge criteria should be interpreted with caution - Jun-wei Su; Wen-rui Wu; Guan-jing Lang; Hong Zhao; Ji-fang Sheng (Journal of Zhejiang University-SCIENCE B, 2020)

Mechanical characteristics of soil-rock mixtures containing macropore structure based on 3D modeling technology - Yong Liu; Shao-rui Sun; Ji-hong Wei; Jing-lei Song; Yong-xiang Yu; Wei He; Ji-xing Zhang (Journal of Mountain Science, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Evaluation of the Biodiversity Conservation Function in Liaohe Delta Wetland, Northeastern China - Wenying Yu; Ruipeng Ji; Xiuzhen Han; Long Chen; Rui Feng; Jinwen Wu; Yushu Zhang (Journal of Meteorological Research, 2020)

Trichosordarin A, a norditerpene glycoside from the marine-derived fungus Trichoderma harzianum R5 - Xiao-Rui Liang; Xin-Yue Ma; Nai-Yun Ji (Natural Product Research, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Antifungal Activity of Magnesium Oxide Nanoparticles: Effect on the Growth and Key Virulence Factors of Candida albicans - Fanzhi Kong; Jiaying Wang; Rui Han; Shuaiqi Ji; Jin Yue; Yongliang Wang; Lei Ma (Mycopathologia, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Transmission risk of patients with COVID-19 meeting discharge criteria should be interpreted with caution - Jun-wei Su; Wen-rui Wu; Guan-jing Lang; Hong Zhao; Ji-fang Sheng (Journal of Zhejiang University-SCIENCE B, 2020)

First report of broad bean wilt virus 2 infection in eggplant in China - Peng-Huan Rui; Lei Jiang; Shuai Li; Xi-Zi Jiang; Qing-Qing Zhao; Ji Ying Feng; Tong Jiang (Journal of Plant Pathology, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Object-Based Mapping of Plastic Greenhouses with Scattered Distribution in Complex Land Cover Using Landsat 8 OLI Images: A Case Study in Xuzhou, China - Li Ji; Lianpeng Zhang; Yang Shen; Xing Li; Wei Liu; Qi Chai; Rui Zhang; Dan Chen (Journal of the Indian Society of Remote Sensing, 2020)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Purification and enzymatic characterization of the RNA ligase RTCB from Thermus thermophilus - Shuyan Duan; Zijun Chen; Zhengyang Li; Rui Ji; Jianhua Gan; Jixi Li (Biotechnology Letters, 2019)

Lithological identification with probabilistic distribution by the modified compositional Kriging - Feilong Han; Hongbing Zhang; Qiang Guo; Jianwen Rui; Qiuyan Ji (Arabian Journal of Geosciences, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Responses of nitrification and denitrification to nitrogen and phosphorus fertilization: does the intrinsic soil fertility matter? - Ying Wang; Hongfei Ji; Rui Wang; Shengli Guo (Plant and Soil, 2019)

Effects of different substrates on nitrogen and phosphorus removal in horizontal subsurface flow constructed wetlands - Rui Xu; Yong Zhang; Rong Liu; Yun Cao; Guoxiang Wang; Lingchen Ji; Yifan Xu (Environmental Science and Pollution Research, 2019)

The Construction of Full-Length cDNA Library for Otodectes cynotis - Li Hu; Ya-e Zhao; Dong-ling Niu; Rui Yang; Ji-hui Zeng (Acta Parasitologica, 2019)

Dynamic Impedances of Offshore Rock-Socketed Monopiles - Rui He; Ji Ji; Jisheng Zhang; Wei Peng; Zufeng Sun; Zhen Guo (Journal of Marine Science and Engineering, 2019)
With the development of offshore wind energy in China, more and more offshore wind turbines are being constructed in rock-based sea areas. However, the large diameter and thin-walled steel rock-socketed monopiles are very scarce at present, and both the construction and design are very difficult. For the design, the dynamic safety during the whole lifetime of the wind turbine is difficult to guarantee. Dynamic safety of a turbine is mostly controlled by the dynamic impedances of the rock-socketed monopile, which are still not well understood. How to choose the appropriate impedances of the socketed monopiles so that the wind turbines will neither resonant nor be too conservative is the main problem. Based on a numerical model in this study, the accurate impedances are obtained for different frequencies of excitation, different soil and rock parameters, and different rock-socketed lengths. The dynamic stiffness of monopile increases, while the radiative damping decreases as rock-socketed depth increases. When the weathering degree of rock increases, the dynamic stiffness of the monopile decreases, while the radiative damping increases.

Antioxidant defense against rust infection in the leaf tissue of Malus crabapple - Yudan Duan; Suxiao Hao; Rui Luo; Yanfen Lu; Ge Li; Jie Zhang; Ji Tian; Yuncong Yao (Acta Physiologiae Plantarum, 2019)

An Innovative Sampling Method for Determining the Scale Effect of Rock Joints - Rui Yong; Ji-Bo Qin; Man Huang; Shi-Gui Du; Jie Liu; Gao-Jian Hu (Rock Mechanics and Rock Engineering, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

Relative Telomere Length and Stroke Risk in a Chinese Han Population - Dan Gao; Rui Zhang; Guofa Ji; Chunqi Li; Dangshe Guo; Tianbo Jin; Mingwei Chen (Journal of Molecular Neuroscience, 2018)

Role of simvastatin in tumor lymphangiogenesis and lymph node metastasis - Rui-Cheng Ji; Yuki Eshita; Takashi Kobayashi; Shinya Hidano; Naganori Kamiyama; Yasuhiko Onishi (Clinical & Experimental Metastasis, 2018)

Neuregulin-1β Plays a Neuroprotective Role by Inhibiting the Cdk5 Signaling Pathway after Cerebral Ischemia-Reperfusion Injury in Rats - Rui Zhang; Cui Liu; Yaqing Ji; Lei Teng; Yunliang Guo (Journal of Molecular Neuroscience, 2018)

Land-use change alters patterns of soil biodiversity in arid lands of northwestern China - Feng-Rui Li; Ji-Liang Liu; Wei Ren; Lu-Lu Liu (Plant and Soil, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Comprehensive drought index as an indicator for use in drought monitoring integrating multi-source remote sensing data: a case study covering the Sichuan-Chongqing region - Tao Ji; Guosheng Li; Hua Yang; Rui Liu; Tairong He (International Journal of Remote Sensing, 2018)

Growth Differentiation Factor 15 Is a Novel Diagnostic Biomarker of Mitochondrial Diseases - Xinbo Ji; Lizhen Zhao; Kunqian Ji; Yuying Zhao; Wei Li; Rui Zhang; Ying Hou; Jianqiang Lu; Chuanzhu Yan (Molecular Neurobiology, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Development and characterization of 32 SNP markers for the northern snakehead (Channa argus) using high resolution melting (HRM) - Bo-Chi Zhang; Gui-Rong Zhang; Wei Ji; Rui-Bin Yang; Gui-Wei Zou; Kun-Ci Chen; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics Resources, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Nominal effective immunoreaction volume of magnetic beads at single bead level - Rui Wang; Yuan Chen; Kai Fan; Feng Ji; Jian Wu; Yong-hua Yu (Journal of Zhejiang University-SCIENCE B, 2017)

Improved GNSS-based indoor positioning algorithm for mobile devices - Rui Xu; Wu Chen; Ying Xu; Shengyue Ji; Jianye Liu (GPS Solutions, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Formation and evolution of Emeishan basalt saprolite in vadose zones of Touzhai landslide source rockmass - Ji-qing Yang; Ze-min Xu; Rui Zhang; Ji-pu Chen; Zhe Ren; Rong-zhang Luo; Xiu-shuo Zhang (Journal of Mountain Science, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Warming Effects on Ecosystem Carbon Fluxes Are Modulated by Plant Functional Types - Ji Chen; Yiqi Luo; Jianyang Xia; Kevin R. Wilcox; Junji Cao; Xuhui Zhou; Lifen Jiang; Shuli Niu; Katerina Y. Estera; Rujin Huang; Feng Wu; Tafeng Hu; et al. (Ecosystems, 2017)

Costimulation of soil glycosidase activity and soil respiration by nitrogen addition - Ji Chen; Yiqi Luo; Jianwei Li; Xuhui Zhou; Junji Cao; Rui‐Wu Wang; Yunqiang Wang; Shelby Shelton; Zhao Jin; Laura M. Walker; Zhaozhong Feng; Shuli Niu; et al. (Global Change Biology, 2017)
Unprecedented levels of nitrogen (N) have been deposited in ecosystems over the past century, which is expected to have cascading effects on microbially mediated soil respiration ( SR ). Extracellular enzymes play critical roles on the degradation of soil organic matter, and measurements of their activities are potentially useful indicators of SR . The links between soil extracellular enzymatic activities ( EEA s) and SR under N addition, however, have not been established. We therefore conducted a meta‐analysis from 62 publications to synthesize the responses of soil EEA s and SR to elevated N. Nitrogen addition significantly increased glycosidase activity ( GA ) by 13.0%, α ‐1,4‐glucosidase ( AG ) by 19.6%, β ‐1,4‐glucosidase ( BG ) by 11.1%, β ‐1,4‐xylosidase ( BX ) by 21.9% and β ‐D‐cellobiosidase ( CBH ) by 12.6%. Increases in GA were more evident for long duration, high rate, organic and mixed N addition (combination of organic and inorganic N addition), as well as for studies from farmland. The response ratios ( RR s) of GA were positively correlated with the SR ‐ RR s, even when evaluated individually for AG , BG , BX and CBH . This positive correlation between GA ‐ RR and SR ‐ RR was maintained for most types of vegetation and soil as well as for different methods of N addition. Our results provide the first evidence that GA is linked to SR under N addition over a range of ecosystems and highlight the need for further studies on the response of other soil EEA s to various global change factors and their implications for ecosystem functions.

Sequence analysis and expression profiles of TaABI5, a pre-harvest sprouting resistance gene in wheat - Ke Zhou; Jian Yang; Zao-Xia Wang; Ji-Rui Wang (Genes & Genomics, 2017)

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Tissue Transglutaminase and Its Product Isopeptide Are Increased in Alzheimer’s Disease and APPswe/PS1dE9 Double Transgenic Mice Brains - Ji Zhang; Suqing Wang; Wei Huang; David A. Bennett; Dennis W. Dickson; Dengshun Wang; Rui Wang (Molecular Neurobiology, 2016)

Characterization and expression analyses of the H+-pyrophosphatase gene in rye - CHANG-SHUI WANG; QIAN-TAO JIANG; JIAN MA; XIU-YING WANG; JI-RUI WANG; GUO-YUE CHEN; PENG-FEI QI; YUAN-YING PENG; XIU-JIN LAN; YOU-LIANG ZHENG; YU-MING WEI (Journal of Genetics, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Trichocitrin, a new fusicoccane diterpene from the marine brown alga-endophytic fungus Trichoderma citrinoviride cf-27 - Xiao-Rui Liang; Feng-Ping Miao; Yin-Ping Song; Zhan-Yong Guo; Nai-Yun Ji (Natural Product Research, 2016)

Archaeal communities in the sediments of different mangrove stands at Dongzhaigang, China - Wei Li; Wei Guan; Huai Chen; Baowen Liao; Ji Hu; Changhui Peng; Junpeng Rui; Jianqing Tian; Dan Zhu; Yixin He (Journal of Soils and Sediments, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Advanced oxidation protein products induce chondrocyte apoptosis via receptor for advanced glycation end products-mediated, redox-dependent intrinsic apoptosis pathway - Qian Wu; Zhao-Ming Zhong; Si-Yuan Zhu; Cong-Rui Liao; Ying Pan; Ji-Huan Zeng; Shuai Zheng; Ruo-Ting Ding; Qing-Song Lin; Qing Ye; Wen-Bin Ye; Wei Li; et al. (Apoptosis, 2016)

Molecular identification and expression of the Foxl2 gene during gonadal sex differentiation in northern snakehead Channa argus - Dan-Dan Wang; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Fish Physiology and Biochemistry, 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Effect of irrigation on the soil respiration of constructed grasslands in Inner Mongolia, China - Ji–Rui Gong; Sha Xu; Yihui Wang; Qinpu Luo; Min Liu; Wei Zhang (Plant and Soil, 2015)

Atrokylindriopsis, a new genus of hyphomycetes from Hainan, China, with relationship to Chaetothyriales - Ying-Rui Ma; Ji-Wen Xia; Jian-Mei Gao; Xiang-Yu Li; Rafael F. Castañeda Ruíz; Xiu-Guo Zhang; Zhuang Li (Mycological Progress, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Mertk deficiency alters expression of micrornas in the retinal pigment epithelium cells - Yong Tang; Qingjun Lu; Yunrong Wei; Lixia Han; Rui Ji; Qiutang Li; Qingxian Lu (Metabolic Brain Disease, 2015)

(Z)-3-Hexenal, One of the Green Leaf Volatiles, Increases Susceptibility of Rice to the White-Backed Planthopper Sogatella furcifera - Baohui Wang; Guoxin Zhou; Zhaojun Xin; Rui Ji; Yonggen Lou (Plant Molecular Biology Reporter, 2015)

TAM receptor deficiency affects adult hippocampal neurogenesis - Rui Ji; Lingbin Meng; Qiutang Li; Qingxian Lu (Metabolic Brain Disease, 2015)

Role of neurotrophin in the taste system following gustatory nerve injury - Lingbin Meng; Xin Jiang; Rui Ji (Metabolic Brain Disease, 2015)

A comprehensive meta-analysis of association between genetic variants of GDF5 and osteoarthritis of the knee, hip and hand - Rui Zhang; Jianfeng Yao; Peng Xu; Baohu Ji; James V. Luck; Brian Chin; Shemin Lu; John R. Kelsoe; Jie Ma (Inflammation Research, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Medicinal facilities to B16F10 melanoma cells for distant metastasis control with a supramolecular complex by DEAE-dextran-MMA copolymer/paclitaxel - Yuki Eshita; Rui-Cheng Ji; Masayasu Onishi; Takashi Kobayashi; Masaaki Mizuno; Jun Yoshida; Naoji Kubota; Yasuhiko Onishi (Drug Delivery and Translational Research, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

LSM14A inhibits porcine reproductive and respiratory syndrome virus (PRRSV) replication by activating IFN-β signaling pathway in Marc-145 - Zhenhong Li; Rui Chen; Jinhua Zhao; Ziyu Qi; Likai Ji; Yueran Zhen; Bang Liu (Molecular and Cellular Biochemistry, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Expression and prognostic role of SGTA in human breast carcinoma correlates with tumor cell proliferation - Ting Zhu; Zhengxiang Ji; Caixia Xu; Zhiyang Peng; Liang Gu; Rui Zhang; Yangchen Liu (Journal of Molecular Histology, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Simulation and causes of eastern Antarctica surface cooling related to ozone depletion during austral summer in FGOALS-s2 - Jing Yang; Qing Bao; Duoying Ji; Daoyi Gong; Rui Mao; Ziyin Zhang; Seong-Joong Kim (Advances in Atmospheric Sciences, 2014)

Ergosteroid derivatives from an algicolous strain of Aspergillus ustus - Xiang-Hong Liu; Feng-Ping Miao; Xiao-Rui Liang; Nai-Yun Ji (Natural Product Research, 2014)

A new alkaloid from the fruit of Nandina domestica Thunb. - Cai-Ying Peng; Jian-Qun Liu; Rui Zhang; Ji-Cheng Shu (Natural Product Research, 2014)

Two new species of Spadicoides and Gangliostilbe from southern China - Li-Guo Ma; Ji-Wen Xia; Ying-Rui Ma; Rafael F. Castañeda-Ruíz; Xiu-Guo Zhang (Mycological Progress, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Rapamycin inhibition of CFA-induced lymphangiogenesis in PLN is independent of mast cells - Rui-Cheng Ji; Yuki Eshita (Molecular Biology Reports, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Wheat gene TaS3 contributes to powdery mildew susceptibility - Shaohui Li; Rui Ji; Robert Dudler; Mingli Yong; Qide Deng; Zhengyi Wang; Dongwei Hu (Plant Cell Reports, 2013)

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Litorilituus sediminis gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Yan Wang; Rui Zhao; Shiqi Ji; Zhao Li; Tong Yu; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Roseovarius marisflavi sp. nov., isolated from an amphioxus breeding zone in the coastal region of the Yellow Sea, China - Zhao Li; Rui Zhao; Shiqi Ji; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

Shrubs and species identity effects on the distribution and diversity of ground-dwelling arthropods in a Gobi desert - Feng-Rui Li; Ji-Liang Liu; Chang-An Liu; Qi-Jun Liu; Rui-Xue Niu (Journal of Insect Conservation, 2013)

Identification of 40k γ-secalin genes - PENG-FEI QI; QING CHEN; THÉRÈSE OUELLET; CHENG-XING LE; JIA AI; YU-MING WEI; JI-RUI WANG; YOU-LIANG ZHENG (Journal of Genetics, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Litoribacillus peritrichatus gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Rui Zhao; Shiqi Ji; Yan Wang; Tong Yu; Zhao Li; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

Over-expression of integrin-linked kinase correlates with aberrant expression of Snail, E-cadherin and N-cadherin in oral squamous cell carcinoma: implications in tumor progression and metastasis - Dan Zhao; Xiu-Fa Tang; Kai Yang; Ji-Yuan Liu; Xiang-Rui Ma (Clinical & Experimental Metastasis, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Influences of shrub vegetation on distribution and diversity of a ground beetle community in a Gobi desert ecosystem - Ji-Liang Liu; Feng-Rui Li; Chang-An Liu; Qi-Jun Liu (Biodiversity and Conservation, 2012)

Haplotype variations of gene Ppd-D1 in Aegilops tauschii and their implications on wheat origin - Lin Huang; Qing Wang; Lian-Quan Zhang; Zhong-Wei Yuan; Ji-Rui Wang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Pharmacological kinetics of BmK AS, a sodium channel site 4-specific modulator on Nav1.3 - Zhi-Rui Liu; Jie Tao; Bang-Qian Dong; Gang Ding; Zhi-Jun Cheng; Hui-Qiong He; Yong-Hua Ji (Neuroscience Bulletin, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

siRNAs target sites selection of ezrin and the influence of RNA interference on ezrin expression and biological characters of osteosarcoma cells - XiFu Shang; YaoFei Wang; QiChun Zhao; KeRong Wu; Xu Li; XiaoFeng Ji; Rui He; WenZhi Zhang (Molecular and Cellular Biochemistry, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Gel microbead cultivation with a subenrichment procedure can yield better bacterial cultivability from a seawater sample than standard plating method - Shiqi Ji; Rui Zhao; Qi Yin; Yuan Zhao; Chenguang Liu; Tian Xiao; Xiaohua Zhang (Journal of Ocean University of China, 2012)

Comparison of initial hydrolysis of the three dimethyl phthalate esters (DMPEs) by a basidiomycetous yeast, Trichosporon DMI-5-1, from coastal sediment - Zhu-Hua Luo; Yi-Rui Wu; Ka-Lai Pang; Ji-Dong Gu; Lilian L. P. Vrijmoed (Environmental Science and Pollution Research, 2011)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Echinococcus granulosus: Immunoprotection accompanyied by humoral and cytokine response against secondary hydatidosis in mice immunized with rEg.myophilin - Junfeng Sun; Yana Wang; Zongji Li; Rui Ma; Haiqing Ji; Ying Xiong; Yin Wang; Zhaoyu Li; Wei Zhao (Veterinary Research Communications, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Nash model parameter uncertainty analysis by AM-MCMC based on BFS and probabilistic flood forecasting - Zhenxiang Xing; Xiaofang Rui; Qiang Fu; Yi Ji; Shijiang Zhu (Chinese Geographical Science, 2011)

Multiple induced mutagenesis for improvement of ethanol production by Kluyveromyces marxianus - Zong-wen Pang; Jing-juan Liang; Xiao-juan Qin; Ji-rui Wang; Jia-xun Feng; Ri-bo Huang (Biotechnology Letters, 2010)

RETRACTED ARTICLE: Cytotoxic activities of tubeimoside-2 on human hepatoma HepG2 cells by induction of G2/M phase arrest and apoptosis in a p53-dependent manner - Ying-Yong Zhao; Xu Chao; Yongmin Zhang; Li-Jun Sun; Hong Zhang; Rui-Chao Lin; Xuefeng Shen; Wen-Ji Sun (Apoptosis, 2010)

Genome-wide identification and evaluation of novel internal control genes for Q-PCR based transcript normalization in wheat - Xiang-Yu Long; Ji-Rui Wang; Thérèse Ouellet; Hélène Rocheleau; Yu-Ming Wei; Zhi-En Pu; Qian-Tao Jiang; Xiu-Jing Lan; You-Liang Zheng (Plant Molecular Biology, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Identification, localization, and characterization of putative USP genes in barley - Wei-Tao Li; Yu-Ming Wei; Ji-Rui Wang; Chun-Ji Liu; Xiu-Jin Lan; Qian-Tao Jiang; Zhi-En Pu; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

A possible role of myristoylated alanine-rich C kinase substrate in endocytic pathway of Alzheimer’s disease - Rui Su; Zhen-Yun Han; Ji-Ping Fan; Yun-Ling Zhang (Neuroscience Bulletin, 2010)

The formation and evolution of Chepaizi-Mosuowan paleo-uplift and its control on the distributions of sedimentary facies in the Junggar Basin - YouLiang Ji; Yong Zhou; Jun Kuang; Lu Wan; Rui Zhang; ChunHong Lu (Science China Earth Sciences, 2010)

Molecular diversity and phylogenetic analyses of y-type high-molecular-weight glutenin promoters from different genomes in Triticeae - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Plant Systematics and Evolution, 2010)

Evolution of viviparity in cold-climate lizards: testing the maternal manipulation hypothesis - Hong Li; Yan-Fu Qu; Rui-Bin Hu; Xiang Ji (Evolutionary Ecology, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Embryo and anther regulation of the mabinlin II sweet protein gene in Capparis masaikai Lévl - Xin-Wen Hu; Si-Xin Liu; Jian-Chun Guo; Ji-Tao Li; Rui-Jun Duan; Shao-Ping Fu (Functional & Integrative Genomics, 2009)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Molecular Characterization of the pina Gene in Einkorn Wheat - Qing Chen; Peng-Fei Qi; Yu-Ming Wei; Ji-Rui Wang; You-Liang Zheng (Biochemical Genetics, 2009)

Degraded vegetation and wind erosion influence soil carbon, nitrogen and phosphorus accumulation in sandy grasslands - Feng-Rui Li; Wen-Zhi Zhao; Ji-Liang Liu; Zhi-Gang Huang (Plant and Soil, 2009)

Mechanisms underlying low [Ca2+]o-induced increased excitability of hippocampal neurons - Wei-Dong Yue; Yun-Hong Zhang; Feng Gu; Jing Wang; Ji-Ye Zhang; Rui-Min Gu (Neuroscience Bulletin, 2008)

SNP and haplotype identification of the wheat monomeric α-amylase inhibitor genes - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Genetica, 2008)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

Sequence Variations and Haplotype Identification of Wheat Dimeric α-Amylase Inhibitor Genes in Einkorn Wheats - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Biochemical Genetics, 2007)

Testicular germ cell tumor susceptibility genes from the consomic 129.MOLF-Chr19 mouse strain - Rui Zhu; Yuan Ji; Lianchun Xiao; Angabin Matin (Mammalian Genome, 2007)

Genetic dissection of plant height by molecular markers using a population of recombinant inbred lines in maize - Tang Ji-hua; Teng Wen-tao; Yan Jian-bing; Ma Xi-qing; Meng Yi-jiang; Dai Jin-rui; Li Jian-Sheng (Euphytica, 2007)

Lymphatic endothelial cells, tumor lymphangiogenesis and metastasis: New insights into intratumoral and peritumoral lymphatics - Rui-Cheng Ji (Cancer and Metastasis Reviews, 2007)

The effects of flooding on several hybrid poplar clones in Northern China - Ji-Rui Gong; Xin-Shi Zhang; Yong-Mei Huang; Chun-Lai Zhang (Agroforestry Systems, 2007)

Genetic mapping of the wheat dimeric α-amylase inhibitor multi-gene family using allele-specific primers based on intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2006)

Characterization of two HMW glutenin subunit genes from Taenitherum Nevski - Ze-Hong Yan; Yu-Ming Wei; Ji-Rui Wang; Deng-Cai Liu; Shou-Fen Dai; You-Liang Zheng (Genetica, 2006)

A high-molecular-weight glutenin subunit gene 1Dx2.1 from Xinjiang rice wheat - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Cereal Research Communications, 2005)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

Biophysical studies of a ruthenium(II) polypyridyl complex binding to DNA and RNA prove that nucleic acid structure has significant effects on binding behaviors - Hong Xu; Yi Liang; Peng Zhang; Fen Du; Bing-Rui Zhou; Jun Wu; Jian-Hong Liu; Zhi-Gang Liu; Liang-Nian Ji (JBIC Journal of Biological Inorganic Chemistry, 2005)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

A Chimeric Ecdysone Receptor Facilitates Methoxyfenozide-Dependent Restoration of Male Fertility in ms45 Maize - Erica Unger; A. Mark Cigan; Mary Trimnell; Rui-ji Xu; Tim Kendall; Brad Roth; Marc Albertsen (Transgenic Research, 2002)

Selection and orientation of adjacent genes influences DAM-mediated male sterility in transformed maize - Erica Unger; Steve Betz; Rui-ji Xu; A. Mark Cigan (Transgenic Research, 2001)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)